Lithium-sulfur battery cathode and sodium-sulfur battery cathode
By using defective metal organic frame materials in lithium-sulfur batteries and sodium-sulfur batteries to capture lithium ions or polysulfides, the problems of polysulfide dissolution and insoluble sulfide formation in battery cycles are solved, achieving higher capacity retention and cycle life.
Patent Information
- Application Number
- CN201980044412.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-04-30
- Filing Date
- 2019-04-29
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2039-04-29
AI Technical Summary
Lithium-sulfur batteries and sodium-sulfur batteries have problems with polysulfide dissolution and insoluble sulfide formation during the charging and discharge cycles, resulting in irreversible capacity loss and poor battery cycle life.
Using defective metal organic frame materials, lithium ions are captured by defects in structural defects and constituent features or chemical anchor substituents used to capture polysulfides, thereby improving battery performance.
The absolute capacity and capacity retention of lithium-sulfur batteries and sodium-sulfur batteries are improved, the cycle life is extended, and the dissolution of polysulfides and the loss of reactive sulfur are reduced.
Smart Images

Figure CN112352334B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Provisional Application No. 62 / 664,371, filed on April 30, 2018, the contents of which are incorporated by reference in their entirety. Background of the Invention
[0004] The field of the invention relates generally to high capacity lithium-sulfur batteries and ambient temperature sodium-sulfur batteries.
[0005] Lithium-sulfur (Li-S) batteries have become based on the approximately 300 Wh kg -1 Compared to about 2600Wh kg -1 Sulfur is a promising competitor for high energy density Li-ion batteries. In addition, sulfur is an abundant and inexpensive raw material and can solve the supply and cost issues associated with LiCoO2 cathodes in Li-ion batteries.
[0006] Li-S batteries include a cathode containing sulfur, an anode containing lithium, and an electrolyte. During the battery discharge cycle, polysulfides are reduced on the cathode surface, for example, in the following sequence:
[0007] S8→Li2S8→Li2S6→Li2S4→LiS3 · →Li2S2→Li2S
[0008] During the battery charge cycle, polysulfides are formed at the cathode, for example, according to the following sequence:
[0009] Li2S→Li2S2→LiS3 · →Li2S4→Li2S6→Li2S8→S8.
[0010] More specifically, during a typical discharge cycle in a Li-S cell, energy is obtained from the oxidation of the Li anode to form Li + These Li ions migrate across the electrolyte to the sulfur cathode (e.g., sulfur / carbon composite), and the charge converts the sulfur to polysulfide Li2S x (where x = 1-8) reduction equilibrium.
[0011] Although the Li-S conversion chemistry promotes about 1680 mAh g -1Although Li-S devices have a high theoretical charge capacity, the problem is that there are significant challenges in Li-S devices that have hindered commercialization. For example, sulfur is a poor conductor of both ions and electrons, which reduces the maximum capacity of the battery. In addition, the dissolution of polysulfides from the sulfur cathode into the electrolyte leads to the depletion of active sulfur and the formation of insoluble and insulating sulfide species on the surface of the anode and cathode during repeated charge and discharge cycles. This phenomenon, known as "polysulfide shuttle", leads to irreversible capacity loss and poor battery cycle life.
[0012] To address the issues associated with Li-S batteries, a variety of cathode materials have been investigated to enhance conductivity and maximum charge capacity. For example, Li2S has been shown to improve Li ion conductivity and produce high sulfur utilization (defined as the amount of sulfur available for redox chemistry). Li-rich cathodes provide an alternative to existing Li + Sites are used to promote ion conduction. See, for example: Z. Lin et al., Lithium Superionic Sulfide Cathode for All-Solid Lithium-Sulfur Batteries, ACS Nano, 2013, 7, 2829-2833; and L. Wang et al., A high performance lithium-ion sulfur battery based on a Li2S cathode using adual-phase electrolyte, Energy Environ. Sci., 2015, 8, 1551-1558. However, the Li2S cathode still suffers from polysulfide leaching and high overpotential. In addition, attempts to incorporate solid lithium thiophosphate materials into electrodes to provide high ionic conductivity have proven to be impractical due to material instability. See, for example, Z. Lin et al., Lithium polysulfidophosphates: a family of lithium-conducting sulfur-rich compounds for lithium-sulfur batteries, Angew. Chem. Int. Ed. Engl., 2013, 52, 7460-3.
[0013] Ambient temperature (room temperature) sodium-sulfur batteries (RT Na-S) are also promising due to their high theoretical energy density and low cost. Moreover, compared with lithium batteries, RT Na-S batteries avoid the use of relatively expensive Li in favor of Na.
[0014] The RT Na-S battery comprises a cathode comprising sulfur, an anode comprising sodium metal, and an electrolyte. During the battery discharge cycle, polysulfides are reduced on the cathode surface, and during the battery charge cycle, polysulfides are formed at the cathode as follows:
[0015]
[0016] As with Li-S batteries, there are significant challenges in RT Na-S devices that have hindered commercialization, such as achieving a charge capacity close to the theoretical value and maintaining the charge through repeated cycling.
[0017] Therefore, there is a need in the art for Li-S batteries and RT Na-S batteries with improved capacity and charge retention.
[0018] Brief description of the invention
[0019] In one aspect of the present disclosure, a battery cathode is provided. The cathode comprises a plurality of defective metal organic framework portions: (i) wherein each defective metal organic framework portion independently comprises at least one defect selected from structural defects and compositional features; and (ii) wherein each defect independently allows for the capture of battery anode metal ions, the incorporation of chemical anchor substituents for the capture of polysulfides, or a combination thereof.
[0020] In another aspect of the present disclosure, a lithium-sulfur battery is provided. The battery comprises: (i) an anode comprising lithium; (ii) an electrolyte; and (iii) a cathode comprising sulfur and a plurality of defective metal-organic framework moieties, (1) wherein each defective metal-organic framework moiety independently comprises at least one defect selected from structural defects and compositional features; and (2) wherein each defect independently allows for the capture of anode metal ions of the battery or incorporates a chemical anchor substituent for the capture of polysulfides.
[0021] In another aspect of the present disclosure, a solid material having lithium conductivity is provided. The solid material includes lithium and a plurality of defective metal-organic framework portions: (i) wherein each defective metal-organic framework portion independently includes a defect selected from a metal coordination site, a compositional feature, and a proton site; and (ii) wherein the lithium is bound to or trapped by the defect.
[0022] In yet another aspect of the present disclosure, a method for using a lithium-sulfur battery is provided. The method includes providing a lithium-sulfur battery having a charge cycle and a discharge cycle. In some aspects: (1) the battery includes (a) an anode comprising lithium, (b) an electrolyte, and (c) a cathode comprising sulfur and a plurality of defective metal-organic framework portions, wherein the plurality of defective metal-organic framework portions include at least one defect selected from structural defects and compositional features, wherein each defect independently allows for the capture of lithium ions; (2) the discharge cycle includes reducing elemental sulfur and / or lithium polysulfide to lithium sulfide at the cathode, wherein at least a portion of the lithium polysulfide is captured by the defective metal-organic framework portion; and (3) the charge cycle includes oxidizing the lithium sulfide to lithium polysulfide and / or elemental sulfur at the cathode, wherein at least a portion of the lithium polysulfide in the oxidation reaction is the lithium polysulfide captured in the discharge cycle. In some aspects: (1) a lithium-sulfur battery comprises (a) an anode comprising lithium, (b) an electrolyte, and (c) a cathode comprising sulfur and a plurality of defective metal-organic framework portions, wherein the plurality of defective metal-organic framework portions comprise at least one defect selected from a metal coordination site and a chemical anchor substituent capable of functionalizing a polysulfide thereto; (2) a discharge cycle comprises reducing elemental sulfur and / or lithium polysulfide to lithium sulfide at the cathode, wherein at least a portion of the polysulfide is trapped in the metal-organic framework chemical anchor site by functionalization; and (3) a charge cycle comprises oxidizing the lithium sulfide to lithium polysulfide and / or elemental sulfur at the cathode, wherein at least a portion of the lithium polysulfide in the oxidation reaction is the lithium polysulfide trapped in the discharge cycle. In some aspects: (1) a lithium-sulfur battery comprises (a) an anode comprising lithium, (b) an electrolyte, and (c) a cathode comprising sulfur and (I) a plurality of defective metal-organic framework portions comprising at least one defect selected from structural defects and compositional features, wherein each defect independently allows for the capture of lithium ions, and (II) a plurality of defective metal-organic framework portions comprising at least one defect selected from metal coordination sites and chemical anchor substituents capable of functionalizing polysulfides thereto; (2) a discharge cycle comprises reducing elemental sulfur and / or lithium polysulfide to lithium sulfide at the cathode, wherein at least a portion of the lithium polysulfide is captured in the metal-organic framework chemical anchor sites by functionalization; and (3) a charge cycle comprises oxidizing the lithium sulfide to lithium polysulfide and / or elemental sulfur at the cathode, wherein at least a portion of the lithium polysulfide in the oxidation reaction is the lithium polysulfide captured during the discharge cycle.
[0023] In yet another aspect of the present disclosure, an ambient temperature sodium-sulfur battery is provided. The battery comprises: (i) an anode comprising sodium; (ii) an electrolyte; and (iii) a cathode comprising sulfur and a plurality of defective metal-organic framework moieties, (1) wherein each defective metal-organic framework moiety independently comprises at least one defect selected from structural defects and compositional features, and (2) wherein each defect independently allows for the capture of cell anode metal ions or incorporates chemical anchor substituents for the capture of polysulfides.
[0024] In another aspect of the present disclosure, a solid material having sodium conductivity is provided. The material includes sodium and a plurality of defective metal organic framework portions: (i) wherein each defective metal organic framework portion independently includes a defect selected from a metal coordination site, a compositional feature, and a proton site; and (ii) wherein sodium is bound to or trapped by the defect.
[0025] In another aspect of the present disclosure, a method of using an ambient temperature sodium-sulfur battery is provided. The method includes providing a sodium-sulfur battery having a charge cycle and a discharge cycle. In some aspects: (1) the battery includes (a) an anode comprising sodium, (b) an electrolyte, and (c) a cathode comprising sulfur and a plurality of defective metal-organic framework portions, the plurality of defective metal-organic framework portions comprising at least one defect selected from structural defects and compositional features, wherein each defect independently allows for the capture of sodium ions; (2) the discharge cycle includes reducing elemental sulfur and / or sodium polysulfide to sodium sulfide at the cathode, wherein at least a portion of the sodium polysulfide is captured by the defective metal-organic framework portion; and (3) the charge cycle includes oxidizing the sodium sulfide to sodium polysulfide and / or elemental sulfur at the cathode, wherein at least a portion of the sodium polysulfide in the oxidation reaction is the sodium polysulfide captured in the discharge cycle. In some aspects: (1) a sodium-sulfur battery comprises (a) an anode comprising sodium, (b) an electrolyte, and (c) a cathode comprising sulfur and a plurality of defective metal-organic framework portions, wherein the plurality of defective metal-organic framework portions comprise at least one defect selected from a metal coordination site and a chemical anchor substituent capable of functionalizing a polysulfide thereto; (2) a discharge cycle comprises reducing elemental sulfur and / or sodium polysulfide to sodium sulfide at the cathode, wherein at least a portion of the polysulfide is trapped in the metal-organic framework chemical anchor site by functionalization; and (3) a charge cycle comprises oxidizing sodium sulfide to sodium polysulfide and / or elemental sulfur at the cathode, wherein at least a portion of the sodium polysulfide in the oxidation reaction is the sodium polysulfide trapped in the discharge cycle. In some aspects: (1) a sodium-sulfur battery comprises (a) an anode comprising sodium, (b) an electrolyte, and (c) a cathode comprising sulfur and (I) a plurality of defective metal-organic framework portions comprising at least one defect selected from structural defects and compositional features, wherein each defect independently allows for the capture of sodium ions, and (II) a plurality of defective metal-organic framework portions comprising at least one defect selected from metal coordination sites and chemical anchor substituents capable of functionalizing polysulfides thereto; (2) a discharge cycle comprises reducing elemental sulfur and / or sodium polysulfide to sodium sulfide at the cathode, wherein at least a portion of the sodium polysulfide is captured in the metal-organic framework chemical anchor sites by functionalization; and (3) a charge cycle comprises oxidizing the sodium sulfide to sodium polysulfide and / or elemental sulfur at the cathode, wherein at least a portion of the sodium polysulfide in the oxidation reaction is the sodium polysulfide captured during the discharge cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 One aspect of the present disclosure for introducing defective sites on a UiO-66 metal-organic framework and lithiating the defective metal-organic framework is depicted.
[0028] Figure 2 One embodiment of a lithium-sulfur battery of the present disclosure is depicted.
[0029] Figure 3 One aspect of the present disclosure is depicted for functionalizing defective sites on UiO-66 metal organic framework clusters with chemical anchors such as Li3PS4 and lithiating the defective metal organic framework clusters.
[0030] Figure 4A Depicted are the specific capacities (mAh g) of lithium-sulfur batteries of the present disclosure having cathodes comprising lithiated metal-organic frameworks (LPS-UiO-66(50Benz) and LPS-UiO66(noMod)) compared to batteries having cathodes comprising non-lithiated metal-organic frameworks (UiO-66(50Benz)) and batteries comprising sulfur-carbon composite cathodes (S / C). -1 ) Constant current cycling results versus cycle number. Figure 4B Depicted are the specific capacities (mAh g) of lithium-sulfur batteries of the present disclosure having cathodes comprising lithiated metal-organic frameworks (2xLPS MOF-808; 1xLPS MOF-808, and 0.7xLPS MOF-808) compared to batteries having cathodes comprising non-lithiated metal-organic frameworks (MOF-808) and batteries comprising S / C composite cathodes. -1 ) Constant current cycling results versus cycle number.
[0031] Figure 5A Transmittance (%) versus wavenumber (cm2) of UiO-66 functionalized with Li3PS4 (“LPS”) chemical anchors compared to the parent defect-free MOF (UiO-66) is plotted. -1 )’s infrared (IR) spectrum results. Figure 5B Transmittance (%) versus wavenumber (cm2) of MOF-808 functionalized with Li3PS4 (“LPS”) chemical anchor compared to the parent defect-free MOF (MOF-808) is plotted. -1 )’s infrared (IR) spectrum results.
[0032] Figure 6 The solution state of LPS-functionalized metal organic framework (LPS-UiO-66(50Benz)) in 1 M sodium hydroxide solution is depicted. 31 P nuclear magnetic resonance (NMR) spectroscopy.
[0033] Fig. 7A and Figure 7B Depicted is the LPS-functionalized UiO-66 ( Fig. 7A ) and the LPS-functionalized MOF-808 of the present disclosure ( Figure 7B) 31 P nuclear magnetic resonance (NMR) spectroscopy.
[0034] Figure 8 An example of a button cell is depicted. In some aspects, the button cell has a cathode that includes a defective metal organic framework of the present disclosure.
[0035] Fig. 9 Powder X-ray diffraction (PXRD) results of counts versus 2°θ position for the lithiated defective metal-organic frameworks (Li-UiO-66(noMod), Li-UiO-66(50Benz), and Li-UiO-66(12TFA)) and the non-lithiated metal-organic framework (UiO-66(50Benz)) of the present disclosure are depicted.
[0036] Fig.10 Plotted are the transmittance (%) versus wavenumber (cm2) of the lithiated defective metal organic framework (Li-UiO-66(50Benz)) and the non-lithiated metal organic framework (UiO-66) of the present disclosure. -1 )’s infrared (IR) spectrum results.
[0037] Fig.11A Thermograph analysis (TGA) results of weight loss (%) versus temperature (°C) of a non-lithiated metal organic framework (UiO-66(50Benz)) are plotted, and Fig. 11B Plotted are TGA results of weight loss (%) versus temperature (° C.) for the lithiated metal-organic framework (Li-UiO-66(50Benz)) of the present disclosure.
[0038] Fig.12 Depicted are atomic absorption spectroscopy (AAS) results of lithium incorporated into the lithiated metal-organic framework (Li-UiO-66(MOD)) of the present disclosure prepared under various lithiation synthesis conditions.
[0039] Fig.13 Depicted are the maximum discharge capacities (mAh g) of various lithium-sulfur batteries of the present disclosure having cathodes comprising lithiated metal-organic frameworks of the present disclosure (Li-UiO-66(50Benz) and Li-UiO-66(12TFA)), lithium-sulfur batteries having cathodes comprising lithiated non-modified metal-organic frameworks (Li-UiO-66(noMod)), lithium-sulfur batteries having cathodes comprising non-lithiated metal-organic frameworks (UiO-66(50Benz)), and lithium-sulfur batteries having cathodes comprising metal-organic frameworks lithiated under harsher chemical conditions (Li-UiO-66(50Benz)-80, Li-UiO-66(50Benz)-nBuLi). -1) and the relative lithium content as measured by atomic absorption spectroscopy.
[0040] Fig.14 The absolute capacity (mAh g) of a lithium-sulfur battery of the present disclosure having a cathode comprising a lithiated metal-organic framework compared to a lithium-sulfur battery having a cathode comprising a non-lithiated metal-organic framework is depicted on the left axis and the associated bottom three lines of the closed shape of the graph. -1 ) and the relationship between the number of battery cycles. Fig.14 The relationship between the coulombic efficiency (%) of the lithium-sulfur battery of the present disclosure having a cathode including a lithiated metal-organic framework compared to a lithium-sulfur battery having a cathode including a non-lithiated metal-organic framework and the number of battery cycles is plotted on the right axis and the open shaped correlation line at the top of the curve.
[0041] Fig.15A Depicted are the relative capacities (mAh g) of lithium-sulfur cells of the present disclosure having a cathode comprising a lithiated metal-organic framework (Li-UiO-66(50Benz)) compared to cells having a cathode comprising a non-lithiated metal-organic framework (UiO-66(50Benz)) at low to moderate charge rates from C / 10 to 2C. -1 ) versus the rate capacity of the number of cycles. Fig. 15B Depicted are the relative capacities (mAh g) of lithium-sulfur cells of the present disclosure having a cathode comprising a lithiated metal-organic framework (Li-UiO-66(50Benz)) compared to cells having a cathode comprising a non-lithiated metal-organic framework (UiO-66(50Benz)) at moderate to high charge rates from C / 2 to 4C. -1 ) versus the rate capacity of the number of cycles.
[0042] Fig.16A The maximum specific capacity (mAh g) of lithium-sulfur batteries of the present disclosure with cathodes comprising lithiated metal-organic frameworks (LPS-UiO-66(50Benz); LPS-UiO66(noMod); 2xLPS MOF-808; 1xLPS MOF-808 and 0.7xLPS MOF-808) compared to batteries with cathodes comprising non-lithiated metal-organic frameworks (UiO-66(50Benz) and MOF-808) and batteries comprising S / C composite cathodes is depicted. -1 ) Compiled galvanostatic cycling results versus lithium weight percent, where increasing Li wt.% correlates to increased LPS incorporation. Fig. 16BDepicted are the capacities (mAh g) at 100x cycles of lithium-sulfur cells of the present disclosure having cathodes comprising lithiated metal-organic frameworks (LPS-UiO-66(50Benz); LPS-UiO-66(noMod); 2xLPS MOF-808; 1xLPS MOF-808 and 0.7xLPS MOF-808) compared to cells having cathodes comprising non-lithiated metal-organic frameworks (UiO-66(50Benz) and MOF-808) and cells comprising S / C composite cathodes. -1 ) Compiled galvanostatic cycling results versus lithium weight percent, where increasing Li wt.% correlates to increased LPS incorporation.
[0043] Fig.17A The specific capacity (mAh g) of a lithium-sulfur battery of the present disclosure having a cathode comprising a lithiated metal-organic framework (LPS-UiO-66(50Benz)) compared to a battery having a cathode comprising a non-lithiated metal-organic framework (UiO-66(50Benz)) and a battery comprising a S / C composite cathode at low to moderate charge rates from C / 10 to 2C is depicted. -1 ) versus the rate capacity of the number of cycles. Fig. 17B The specific capacity (mAh g) of a lithium-sulfur battery of the present disclosure having a cathode comprising a lithiated metal-organic framework (LPS-UiO-66(50Benz)) compared to a battery having a cathode comprising a non-lithiated metal-organic framework (UiO-66(50Benz)) and a battery comprising a S / C composite cathode at moderate to high charge rates from C / 2 to 4C is depicted. -1 ) versus the rate capacity of the number of cycles.
[0044] Fig.18 The bottom three lines and left axis in the graph depict the specific capacity (mAh g) at 1C of lithium-sulfur batteries of the present disclosure having a cathode comprising a lithiated metal organic framework (LPS-UiO-66 (50Benz) and LPS-UiO-66 (noMod)) compared to batteries having a cathode comprising an S / C composite cathode. -1 ) Extended current cycling profile versus cycle number. Fig.18 The line at the top of the graph and the right axis plots the relationship between the coulombic efficiency (%) and the number of cycles at 1C for lithium-sulfur cells of the present disclosure having a cathode comprising a lithiated metal-organic framework (LPS-UiO-66(50Benz) and LPS-UiO-66(noMod)) compared to cells having a cathode comprising an S / C composite cathode.
[0045] Fig.19The NMR spectrum of the Li5P2S6N material of the present disclosure is depicted.
[0046] Fig. 20 The IR spectrum of the Li5P2S6N material of the present disclosure is depicted. DETAILED DESCRIPTION OF THE INVENTION
[0048] According to the present disclosure, it has been found that Li-S batteries and RT Na-S batteries including defective material organic framework (MOF) portions provide improved absolute capacity and improved capacity retention compared to Li-S batteries and RT Na-S batteries known in the art. In some aspects, a high-capacity Li-S battery cathode including a lithiated MOF provides an extended Li-S cycle. In some aspects, a high-capacity RT Na-S battery cathode including a sodium-based MOF provides an extended RT Na-S cycle. In some other aspects, a MOF derived from a chemical anchor provides capture of polysulfides and / or encapsulation of polysulfides, which results in improved Li-S performance by reducing the dissolution of polysulfides in the electrolyte and the accompanying loss of reactive sulfur. In some other aspects, a MOF derived from a chemical anchor provides capture of polysulfides and / or encapsulation of polysulfides, which results in improved RT Na-S performance by reducing the dissolution of polysulfides in the electrolyte and the accompanying loss of reactive sulfur. The Li-S batteries and RT Na-S batteries of the present disclosure achieve an order of magnitude in energy density compared to current Li-ion and RT Na-S technologies, while providing improved battery cycle life and capacity retention compared to current Li-S and RT Na-S technologies.
[0049] In some aspects, the Li-S battery of the present disclosure has at least 800 mAh g -1 , at least 900mAh g -1 , at least 1000mAh g -1 , at least 1100mAh g -1 , at least 1200mAh g -1 , at least 1300mAh g -1 , for example 1320mAh g -1 In some aspects, the Li-S battery of the present disclosure also has at least 800 mAh g after 20 charge-discharge cycles. -1 , at least 900mAh g -1 , at least 1000mAh g -1 , at least 1100mAh g -1 or at least 1200mAh g -1In some aspects, the Li-S battery of the present disclosure has a capacity retention of at least 60%, at least 65%, at least 70%, at least 75%, or at least 80% after 20 charge-discharge cycles.
[0050] As used herein, a "metal node" refers to a cluster comprising two or more metal ions connected by bridging oxide and / or hydroxide ligands. Such a node may be referred to as a secondary binding unit (SBU). A non-limiting example of a metal node is hexa-zirconium oxo-hydroxo.
[0051] As used herein, "metal organic framework" (MOF) refers to a material that is a coordination network comprising one or more metal nodes and clusters thereof coordinated by organic ligands or linkers. MOFs are crystalline and can be characterized by one-dimensional, two-dimensional, or three-dimensional structures.
[0052] MOF structures are porous. In some aspects, MOF structures can be characterized as porous frameworks with voids and can also be characterized by surface area. Typically, MOF structures have a surface area ranging from about 200 m 2 / g、300m 2 / g, 400m 2 / g, about 500m 2 / g, about 600m 2 / g, about 700m 2 / g, about 800m 2 / g, about 900m 2 / g, about 1000m 2 / g, about 1100m 2 / g, about 1200m 2 / g, about 1300m 2 / g, about 1400m 2 / g, about 1500m 2 / g or about 1600m 2 / g, and any range consisting of any of those values, such as from about 200m 2 / g to about 1600m 2 / g or from about 400m 2 / g to about 1600m 2 MOFs with a porosity of 200 Å / g are suitable for the practice of the present invention.
[0053] As used herein, "organic ligand" or "organic linker" refers to a molecule or combination of molecules that includes at least one CH bond and is capable of binding to at least two metal nodes.
[0054] As used herein, “defective MOFs” and “defects” with respect to MOFs refer to the ability to capture / encapsulate metal ions (e.g., Li + ) and / or polysulfide sites. Defects can be structural defects, such as dislocations, local defects, or macroscale defects, where the defects result in one or more MOF voids or vacancies. Other defects can be compositional features, such as metal coordination sites, proton sites for functionalization (e.g., -OH and -OH2), chemical anchors, and substituents functionalized on organic linkers. See, for example, Z. Fang et al., Defect Engineered Metal-Organic Frameworks, Agnew. Chem. Int. Ed. 2015, 54, 7234-7254; D. Pravas et al., MOF Functionalization via Solvent-Assisted Ligand Incorporation: Phosphonates vs Carboxylates, Inorg. Chem. 2015, 54, 2185-2192; and G. Shearer et al., Functionalizing the Defects: Postsynthetic Ligand Exchange in the Metal Organic Framework UIO-66, Chem. Mater. 2016, 28, 7190-7193, the contents of each of which are incorporated herein by reference in their entirety. In any of the various aspects of the present disclosure, at least 50%, at least 75%, or at least 90% of the number of MOF parts in the plurality of MOF parts include at least one defect.
[0055] As used herein and as generally known in the art, defects in the structure of solid materials can be local defects (or point defects), large-scale defects or dislocations. Point defects are generally of atomic size and may be generated by the following items: one or more sites in the lattice structure or metal organic framework are occupied (replaced) by impurities (such as atoms or ions), where such replacement atoms are called extrinsic defects; gaps (vacancies) caused by the lack of atoms, where the gaps are called intrinsic defects; or there are extra atoms or extra ions at one or more lattice structure sites where atoms do not usually appear, where such extra atoms are called intrinsic defects. Dislocations are irregularities in the structure of solid materials and are generated due to changes in the regular ordering of atoms along lines called dislocation lines. Large-scale structural defects (or volume defects or body defects) are generally three-dimensional aggregates of atoms or voids that are large enough to affect the three-dimensional (macro) structure of solid materials, such as can be reflected in one or more solid material properties such as structural mechanical strength, porosity, cracking, and the formation of separate small regions of homogeneous and heterogeneous materials (e.g., due to atomic clusters).
[0056] As used herein, "functionalized MOF" refers to a MOF in which one or more backbone atoms of the organic linker carry pendant functional groups, a MOF functionalized with a chemical anchor (eg, Li3PS4).
[0057] Metal-organic MOFs are tunable materials with the ability to incorporate functionality through the selection of organic linkers and metal ion precursors. The high porosity of MOFs provides the ability to accommodate and stabilize reactive sulfide species and metal ions (e.g., lithium ions), while the associated structural integrity and long-range order provide convenient handling for the detection of intermediates using molecular spectroscopy and single crystal and powder diffraction techniques.
[0058] Although the zirconium MOF and Li + metal ions, but those skilled in the art will recognize that the present disclosure is not narrowly limited and is applicable to any defective MOF suitable for capture / encapsulation of metal ions and polysulfides.
[0059] Sodium-sulfur batteries are known in the art. See, for example and without limitation: K. Kumar et al., Progress and prospects of sodium sulfur batteries: A review, Solid State Ionics 312 (2107) 8-16; A. Douglas et al., Ultrafine Iron Pyrite (FeS2) Nanocrystals Improve Sodium-Sulfur and Lithium-Sulfur Conversion Reactions for Efficient Batteries, ACS Nano, Vol. 9, No. 11, 11156-11165, 2015; and A. Abouimrane, A New Class of Lithium and Sodium Rechargeable Batteries Based on Selenium and Selenium-Sulfur as a Positive Electrode, J. Am. Chem. Soc., 2012, 134, 4505-4508. The contents of each of those documents are incorporated herein in their entirety. Although Li-S batteries are also mentioned herein, those skilled in the art will recognize that the present disclosure is not narrowly limited and can be applied to RT Na-S batteries.
[0060] The metal for MOF is suitably any metal, such as, for example, and without limitation, a transition metal that provides a defective MOF suitable for capture / encapsulation of metal ions and polysulfides. In some aspects, the metal is selected from zirconium, hafnium, cerium, copper, zinc, titanium, iron, vanadium, molybdenum, niobium and chromium and combinations thereof. In some aspects, the metal is selected from a combination of at least two of zirconium, hafnium, cerium, copper, zinc, titanium, iron, vanadium, molybdenum, niobium and chromium. In some aspects, the metal is zirconium.
[0061] In some non-limiting aspects of the present disclosure, the MOF is Zr-based. An example of such a Zr-MOF material is UiO-66. For example, another example of a Zr-MOF material is MOF-808. In some such aspects, the MOF is a porous Zr-based MOF, and the MOF is combined with lithium atoms to serve as a Li-rich MOF / S cathode for a Li-S battery. A typical zirconium MOF node structure consists of hexanuclear Zr clusters connected by bridging oxide and hydroxide ligands. In some aspects, SBUs can be formed in the presence of carboxylic acids, resulting in Zr6(μ3-O)4(μ3-OH)4(RCOO) 12 The general formula of .
[0062] In the case of UiO-66, 1,4-benzenedicarboxylic acid (H2BDC) serves as a bidentate linker (ditopic linker) for forming and connecting the SBU of MOF, wherein all carboxylic acid sites are occupied. See J. Cavka et al., A new zirconiuminorganic building brick forming metal organic frameworks with exceptional stability, J Am Chem Soc. 2008, 130 (42), 13850-13851, the contents of which are incorporated by reference in their entirety. Recent studies have shown that by using competitive carboxylic acids known as modulators, defective sites can be incorporated into the UiO-66 structure in the form of missing linkers. See: GC Shearer et al., Tuned to Perfection: Ironing Out the Defects in Metal-Organic Framework UiO-66, Chem. Mater., 2014, 26, 4068-4071; GC Shearer et al., Functionalizing the Defects: Postsynthetic Lig and Exchange in the Metal Organic Framework UiO-66, Chem. Mater., 2016, 28, 7190-7193; and GC Shearer et al., Defect Engineering: Tuning the Porosity and Composition of the Metal-Organic Framework UiO-66 via Modulated Synthesis, Chem. Mater., 2016, 28, 3749-3761, each of which is incorporated herein by reference in its entirety. Defective UiO-66 exhibits a higher BET surface area than the original MOF (i.e., defect-free MOF) as characterized by the surface, which is an increase of at least 5%, at least 10%, at least 15%, at least 20%, or at least 25%, and contains open Zr sites, where aqua and hydroxo ligands occupy the missing linker sites. These defective sites are reactive and can be further functionalized using other carboxylates or phosphates.See: GC Shearer et al., Chem. Mater., 2016, 28, 7190-7193; GC Shearer et al., Chem. Mater., 2016, 28, 3749-3761; S. Wang et al., General and Direct Method for Preparing Oligonucleotide-Functionalized Metal-Organic Framework Nanoparticles, J Am Chem Soc, 2017, 139, 9827-9830; and P. Deria et al., MOF functionalization via solvent-assisted ligand incorporation: Phosphonates vs carboxylates, Inorg. Chem., 2015, 54, 2185-2192, each of which is incorporated herein by reference in its entirety. According to the present disclosure, such as. Figure 1 As shown, these defect sites are suitable for lithium incorporation by deprotonating the available proton sites in the H2O-ligand and the HO-ligand. In particular, Figure 1 As depicted in , the introduction of a missing linker defect introduces an additional proton that can be exchanged for Li + And generate additional Li + storage sites. This deprotonation method is different from the dehydration of Zr nodes to increase Li + Prior art methods for ionic conductivity and sulfur utilization (e.g., disclosed by R. Ameloot et al., Ionic Conductivity in the Metal-Organic Framework UiO-66 by Dehydration and Insertion of Lithiumtert-Butoxide, Chem.-A Eur. J., 2013, 19, 5533-5536, which is incorporated herein by reference in its entirety).
[0063] The node structure of Zr-MOF is characterized by six metal atoms connected by bridging hydroxyl, oxygen and carboxylate ligands. In a fully coordinated node, 12 carboxylates bridge each Zr atom to its neighboring atoms and prevent interaction with guest species. If a portion of the node carboxylate ligands are removed, the open sites become available for binding guest molecules, providing a synthetic handle for advanced functionalization of metal nodes (see, e.g. Figure 3). Certain Zr-MOFs are able to support these open sites either through the intrinsic crystal structure (for example and without limitation, MOF-808) or by introducing defects using tailored synthesis methods (for example and without limitation, UiO-66).
[0064] In the case of MOF-808, MOF-808 contains Zr6(μ3-O)4(μ3-OH)4(RCOO) 12-x (HCOO) x A hexanuclear Zr cluster of the formula wherein x=5 or 6 is connected by 1,3,5-benzenetricarboxylate (BTC). The formate (HCOO) site can be removed under HCl activation and functionalized with other carboxylic acids and chemical anchors such as thiophosphate. The synthesis of MOF-808 has been reported. See: H. Furukawa et al., Water Adsorption in Porous Metal-Organic Frameworks and Related Materials, J. Am. Chem. Soc. 2014, 136, 4369-4381; and J. Jiang et al., Superacidity in Sulfated Metal-Organic Framework-808, J. Am. Chem. Soc. 2014, 136, 12844-12849, the contents of each of which are incorporated by reference in their entirety. Compared to the parent UiO-66 MOF (defect-free), the defect-free MOF-808 includes at least six more potential water / hydroxyl terminal sites per Zr cluster. It is believed that the introduction of additional defects into MOF-808 can be accomplished using the synthetic methods described herein.
[0065] The organic linker is not narrowly limited and can be suitably any organic linker conventionally used in MOF production. Suitable organic linkers generally include at least two functional groups selected from carboxylic acid, boric acid, amine, nitro, anhydride, hydroxyl and combinations thereof. Organic linkers with two, three or four functional groups are within the scope of the present disclosure. In some aspects, the functional group is selected from carboxylate and hydroxyl and combinations thereof. In one aspect, each functional group is a carbonyl.
[0066] The organic linker may include a straight or branched C 1-20 Alkyl group, C 3-12 In some aspects, the alkyl group is C 1-6 In some aspects, the cycloalkyl group is C 4-6Cycloalkyl. In some aspects, the aromatic moiety can include from 1 to 6 rings. For aromatic moieties with more than one ring, the ring can optionally exist in a spirocyclic or fused configuration. In some aspects, the aromatic moiety includes one or two rings, such as benzyl, naphthyl, pyridyl or bipyridyl. Alkyl, cycloalkyl and aromatic moieties can optionally include one or more heteroatoms selected from N, O, S and Si.
[0067] Examples of suitable organic linker compounds include: BTC; oxalic acid; ethyl oxalic acid; fumaric acid; 1,3,5-benzenetribenzoic acid (BTB); benzeneterbenzoic acid (BBC); 5,15-bis(4-carboxyphenyl)zinc(II)porphyrin (BCPP); 1,4-benzenedicarboxylic acid (H2BDC); 2-amino-1,4-benzenedicarboxylic acid (R3-BDC or H2N BDC); 1,2,4,5-benzene tetracarboxylic acid; 2-nitro-1,4-benzenedicarboxylic acid; 1,1'-azo-diphenyl 4,4'-dicarboxylic acid; cyclobutyl-1,4-benzenedicarboxylic acid (R6-BDC); 1,2,4-benzenetricarboxylic acid; 2,6-naphthalene dicarboxylic acid (NDC); 1,1'-biphenyl 4,4'-dicarboxylic acid (BPDC); 2,2'-bipyridyl-5,5'-dicarboxylic acid; adamantane tetracarboxylic acid (ATC) ; adamantane dibenzoic acid (ADB); adamantane tetracarboxylic acid (ATC); dihydroxy terephthalic acid (DHBDC); biphenyl tetracarboxylic acid (BPTC); tetrahydropyrene 2,7-dicarboxylic acid (HPDC); pyrene 2,7-dicarboxylic acid (PDC); pyrazine dicarboxylic acid; acetylene dicarboxylic acid (ADC); camphor dicarboxylic acid; fumaric acid; pyromellitic acid; 1,4-bis(4-carboxyphenyl)butadiyne; nicotinic acid; and triphenyl dicarboxylic acid (TPDC). In some aspects, the organic linker compound is selected from H2BDC, 2-amino-1,4-benzenedicarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4,5-benzenetetracarboxylic acid and 2-nitro-1,4-benzenedicarboxylic acid or a mixture thereof. In some specific aspects, the organic linker compound is H2BDC.
[0068] In some aspects, a mixture of two or more of the above mentioned linkers can be used to introduce one or more functional groups. For example, aminobenzoic acid can be used to provide a free amine group by using a shorter linker such as oxalic acid.
[0069] The electrolyte is not narrowly limited, and suitable electrolytes are known in the art. Solid electrolytes and liquid electrolytes are within the scope of the present disclosure. See, for example: J. Scheers et al., A review of electrolytes for lithium-sulfur batteries, Journal of Power Sources, 2014, 255(1), 204-218; X. Yu et al., Electrode-Electrolyte Interfaces in Lithium-Sulfur Batteries with Liquid or Inorganic Solid Electrolytes, Acc. Chem. Res., 2017, 50(11), 2653-2660; and X. Judez et al., Review-Solid Electrolytes for Safe and High Energy Density Lithium-Sulfur Batteries: Promises and Challenges, Journal of The Electrochemical Society, 2018, 165(1), the contents of each of which are incorporated by reference in their entirety. In some non-limiting aspects, the electrolyte may suitably include a mixture of ethers, dimethyl sulfoxide, and dimethylformamide. An example of such an electrolyte is lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) dissolved in a mixture of dimethoxyethane and dioxolane.
[0070] In any of the various aspects of the present disclosure and in a non-limiting example of preparing a defective MOF within the scope of the present disclosure, a regulated synthesis method developed by Lillerud et al. can be used to synthesize defective UiO-66 samples using competitive monocarboxylic acids that are then incorporated into the MOF structure (see G. Shearer et al., Functionalizing the Defects: Postsynthetic Ligand Exchange in the MetalOrganic Framework UIO-66, Chem. Mater. 2016, 28, 7190-7193 and GC Shearer et al., Defect Engineering: Tuning the Porosity and Composition of the Metal-Organic Framework UiO-66 via Modulated Synthesis, Chem. Mater., 2016, 28, 3749-3761). The competitive carboxylic acid can then be exchanged with water and hydroxyl ligands to create open sites on the UiO-66Zr6-cluster for further binding or functionalization. By changing the molar ratio of the modulator to the multi-topic carboxylic acid linker used in the synthesis and the modulator strength (e.g., pKa, binding constant), a series of MOFs with controllable defect concentrations can be obtained. By introducing H2O- groups and HO- groups that can be quantified by potential acid-base titration, the increase in missing linker sites is related to the increased number of unstable protons. See MRR Destefano et al., Room-Temperature Synthesis of UiO-66 and Thermal Modulation of Densities of Defect Sites, Chem. Mater., 2017, 29, 1357-1361, the contents of which are incorporated herein by reference in their entirety. The method provides a method for combining the acidic protons of both defect sites and node structures with Li + The ability to exchange to create a stable Li-ion reservoir within the material framework.
[0071] During the reduction of sulfur to polysulfides in Li-S batteries, electron transfer must be accompanied by Li + It is believed, without being bound to any particular theory, that the increase in available sites for lithiation on the MOF framework will lead to faster Li +It is further believed that the high concentration of pre-existing Li ions in the MOF structure will promote the formation and encapsulation of polysulfides through favorable electrostatic interactions. Based on experimental evidence to date, there is a significant increase in the Li concentration in the lithiated defective UiO-66 compared to the parent UiO-66 (i.e., UiO-66 with minimal defects). Further based on experimental evidence to date and in a non-limiting example, by Fig.14 The lithiated defective UiO-66 exemplified by Li-UiO-66 (50Benz) in Figure 5 provides improved Li-S capacity retention compared to the parent UiO-66. Further based on experimental evidence, the lithiated defective UiO-66 provides about 900 mAh g -1 (about 1390Wh kg -1 ), and it is believed that the use of MOFs with lithiated defect sites as hosts for polysulfides improves the Li-S cyclability and provides a specific energy density closer to the theoretical limit.
[0072] According to the present disclosure, the extent of Li incorporation can be controlled by, for example, (i) the concentration of defect sites, (ii) the strength of the base (pKa < 30), and (iii) the temperature used for the synthesis (-77°C to 200°C). According to acid-base titrations performed in aqueous media, the pK values of -OH, -OH, and -OH in UiO-66μ are 2.3, 2.5, and 1.3, respectively. aThe values are 3.52, 6.79 and 8.30, respectively. See RCKlet et al., Evaluation of Bronsted Acidity and Proton Topology in Zr-and Hf-based Metal-Organic Frameworks Using Potentiometric Acid-Base Titration, J.Mater.Chem.A, 2016, 4, 1479-1485, the contents of which are incorporated herein in their entirety. However, it has been found that when the pH deviates from neutrality, the stability of UiO-66 in aqueous media may be affected; both acidic and alkaline conditions may lead to MOF degradation as demonstrated by PXRD and ATR-IR experiments. See Y.Huang et al., Stability and Degradation Mechanisms of Metal-Organic Frameworks Containing the Zr6O4(OH)4 Secondary Building Unit, J.Mater.Chem.A, 2013, 1, 5642-5650, the contents of which are incorporated herein in their entirety. In order to suppress or avoid MOF decomposition, a polar aprotic solvent can be used in a strong alkaline solution to carry out a lithiation procedure. In some aspects, the strong base is an organic lithium base, such as n-butyl lithium. In some aspects, the base is an amine, a hydroxide or an alcohol salt such as pyridine, trimethylamine (TEA) or sodium methoxide. In some such aspects, the polar solvent can be selected from N-methylpyrrolidone, tetrahydrofuran, ethyl acetate, acetone, methanol, ethanol, dimethylformamide (DMF), acetonitrile, dimethyl sulfoxide and propylene carbonate. In one aspect, the solvent is DMF. In some aspects, the lithium source can be from an organic lithium base or a lithium salt, such as but not limited to LiNO3. The lithiation procedure can appropriately have a reaction time of at least 1 hour, at least 4 hours, at least 8 hours, at least 16 hours or at least 24 hours such as, for example, 24 hours.
[0073] As previously disclosed, defect site concentration plays a role in lithium storage capacity. An increased number of defect sites results in more acidic protons. A highly defective MOF will easily undergo H + / Li +Exchange, and have greater lithium content. Based on the experimental evidence so far for the non-limiting examples of Li-UiO-66, Li-UiO-66 (12TFA) and Li-UiO-66 (50Benz), the lithium content of Li-UiO-66, Li-UiO-66 (12TFA) and Li-UiO-66 (50Benz) increases with the increase of defect concentration, such as quantified by Li and Zr atomic absorption spectroscopy (AAS). Further lithiation can also be achieved by increasing the temperature or increasing the strength of the base. For example, the UiO-66 (50Benz) in the solution of LiNO3 and TEA described above contained in DMF is heated to 60 ° C and 80 ° C, resulting in a molar Li concentration increase of 1.3 times and 1.7 times, respectively. Compared with similar room temperature lithiation using TEA, the use of a stronger base n-butyl lithium at room temperature also increases the molar Li content by 1.8 times.
[0074] Based on experimental evidence to date and without being bound to any particular theory, under one theory it is believed that the Li reservoir in the MOF will promote the encapsulation of polysulfides through favorable electrostatic interactions.
[0075] Further based on experimental evidence to date and without being bound to any particular theory, based on the success of using Li-rich cathodes, it is believed that the amount of lithium in the cathode can favorably affect polysulfide encapsulation and Li-S battery performance. The reduction of neutral sulfur (S8) to shorter chain lithium polysulfides requires charge-balancing Li + ion diffusion to achieve high sulfur utilization in Li-S batteries (see Figure 2 ). Increasing the Li content will not only further promote Li ion conduction, but also provide favorable electrostatic interactions to stabilize the charged polysulfides and prevent their dissolution. However, the Li content is not easily adjustable in conventional solid-state materials because it may ultimately affect the lattice energy and cause other structural changes.
[0076] In some aspects of the present disclosure, lithium-defective MOFs are provided that promote metal conduction and electrostatic interaction with polysulfides. In some specific aspects, the Li-S cathode comprises such a lithium-defective MOF. In some such aspects, the defective MOF is a Zr-MOF. The lithiated MOF provides a high capacity sulfur cathode and extended Li-S cycling. Figure 1 A scheme for the lithiation of defective Zr-MOFs is depicted in FIG.
[0077] In some aspects of the present disclosure, lithium-defective MOFs incorporating chemical anchor functional groups for covalent anchoring of polysulfides are provided. In some specific aspects, a Li-S cathode comprises such a lithium-defective MOF. Examples of suitable chemical anchors for polysulfides include: thiophosphates, such as [P x O y S z ] a- , wherein x is 1-3, y is 0-9, z is 1-10, and a is 3-6; thiogermanate, such as [Ge x O y S z ] a- , wherein x is 1-3, y is 0-9, z is 1-10, and a is 3-6; and thioarsenate, such as [As x O y S z ] a- , where x is 1-3, y is 0-9, z is 1-10, and a is 3-6. Based on experimental evidence to date, the defective Zr-MOF is functionalized with a chemical anchor Li3PS4 (LPS). Figure 3 Depicted is the introduction of -OH and -H2O proton defect sites into the connected Zr-UiO-66MOF clusters, deprotonation of the active sites, and lithiation of the deprotonated defective MOF active sites to produce Li-UiO-66(MOD) (wherein UiO-66(MOD) refers to defective UiO-66 synthesized with a modulator (MOD) such as benzoic acid and TFA). Under one theory and without being bound to any particular theory, it is believed that during battery cycling at PS4 3- The unit reversibly forms covalent SS bonds to form P(S z )4 3- . Further based on experimental evidence, such as in Figure 4A and Figure 4B As depicted in the figure, with approximately 1200mAh h -1 (about 1860Wh kg -1 The use of LPS-functionalized Zr-MOF in Li-S cells (LPS-UiO-66(MOD)) provides improved capacity retention compared to the very high capacity of an unfunctionalized defect-free Zr-MOF.
[0078] In some other aspects of the present disclosure, the chemical anchor functional group for covalent anchoring of polysulfide is of the general formula M r P n S0 and M r P n S0X qIn any of the various aspects, M is Li or Na. X is a non-sulfur atom, such as N, O, or a halogen. r is 2 to 9, n is 1 to 3, o is 1 to 8, and q is 1 to 4. Examples of such suitable anchors include Li5P2S6N, Li3PS3O, and Li2PS3Cl. Such lithiated thiophosphate chemical anchors are referred to as LPSN, LPSO, or LPSX. Exemplary NMR and IR spectra of LPSN materials are shown in Fig.19 and Fig. 20 In some other aspects of the present disclosure, the Li-S cathode includes both a lithium-defective MOF as described herein that promotes metal conduction and electrostatic interaction with polysulfides and a lithium-defective MOF as described herein that incorporates chemical anchor functional groups for covalent anchoring of polysulfides.
[0079] This disclosure demonstrates that lithiation of Zr-based MOFs improves the performance of Li-S batteries. -1 The demonstrated high capacity exceeds the best sulfur / carbon electrodes known in the art and approaches the 1680 mAh g of Li-S cells. -1 Theoretical limit of. Li-S battery performance can be demonstrated by constant current cycling studies. One measure of battery performance in Li-S batteries is the maximum charge capacity, which is a reflection of the battery's ability to store charge and is directly related to the total energy density. For the non-limiting example of a defective MOF Li-UiO-66 (MOD), where MOD represents the modifier used in the synthesis of the modifier, it is believed that the additional Li sites promote the reduction of polysulfides and increase the maximum charge capacity. The cycle life metric is measured by the relative capacity after extended constant current cycling. The rate of capacity decay provides insights into the ability of the MOF to retain polysulfides during the discharge cycle. Example
[0080] Example 1: Synthesis of UiO-66(MOD)
[0081] Following the modified procedure, UiO-66-MOD MOF is synthesized with different modifiers (MOD) to incorporate defects. See G. Shearer et al., Chem. Mater. 2016, 28, 7190-7193 and GC Shearer et al., Chem. Mater., 2016, 28, 3749-3761. In a typical synthesis, 1.70 g of ZrCl4 (7.3 mmol) and 1.23 g of H2BDC (7.4 mmol) are added to a 500 mL conical flask containing 200 mL of DMF. Controlled amounts of modifiers trifluoroacetic acid (TFA) and benzoic acid (benz) are added to form UiO-66 (12 TFA), UiO-66 (36 TFA) and UiO-66 (50 Benz), and their defect concentrations are analyzed by atomic absorption spectroscopy, where the results are reported in Table 1 below. For each mixture, the mixture was stirred at 50 ° C for 5 minutes until all reagents were dissolved. Once dissolved, 0.40 mL of H2O was added, and the flask was covered and placed in a preheated oven set to 80 ° C for 1 hour. The oven temperature was then increased to 120 ° C and left for 72 hours. The obtained solid was collected by centrifugation and washed overnight in 150 mL of fresh DMF. The solid was collected again and washed with DMF for more than 2 times for 4 hours in this way. After washing, the MOF powder was dried at 60 ° C overnight.
[0082] Table 1: Relative defect concentrations and the associated number of missing linkers in UiO-66(12TFA), UiO-66(36TFA), and UiO-66(50Benz).
[0083] <![CDATA[Molar ratio of ZrCl4]]> Number of missing linkers UiO-66 0 0 UiO-66(12TFA) 12 1.2 UiO-66(36TFA) 36 2 UiO-66(50Benz) 50 3
[0084] In order to exchange the incorporated modifier, according to the synthesis of the previous adjustment of UiO-66, a process called "HCl activation" is used. See G. Shearer et al., Chem. Mater. 2016, 28, 7190-7193. DMF-HCl solution is prepared using a 600:25 ratio of DMF to 8M HCl (v / v). For every 2g of the obtained UiO-66-MOD, 600mL of this solution is used for the HCl activation process. The HCl activation process can be scaled up or down accordingly. 1g of the as-synthesized and dried MOF powder is added to a 500mL conical flask together with 312.5mL of DMF-HCl solution, the conical flask is covered and placed in a preheated 100°C oven and kept for 48 hours. The solid is collected by centrifugation and washed 3 times in 2 days using 150mL of DMF in the manner described above. After the last wash, the excess DMF was removed and the MOF powder was dried in an oven at 60° C. overnight. Each adjusted synthesis resulted in different yields ranging from 1.5 g to 2.5 g after HCl activation.
[0085] For comparison, Li-UiO-66 (noMod) was also synthesized and activated using the same procedure, except that no modifier was added in the initial UiO-66 synthesis.
[0086] Example 2: Synthesis of Li-UiO-66(MOD)
[0087] Lithium incorporation solution is prepared by dissolving 82mg of LiNO3 (70mmol) in 10.5mL of DMF. Once dissolved, 6.3mL of triethylamine (TEA, 45mmol) is added to the solution as a base for deprotonation. The solution is then added to a 20mL scintillation vial containing about 150mg of HCl-activated UiO-66 (MOD), followed by shaking to mix. The mixture is allowed to react (e.g., at room temperature or in an oven set to 60°C or 80°C for 24 hours). After 24 hours, the solution is poured out and replaced with 20mL of acetone. The solid is collected by centrifugation, washed with 20mL of acetone, and allowed to soak in a new acetone solution overnight. The solid is washed with acetone more than four times, and after an additional wash, the solid is soaked in acetone overnight. After the acetone wash, the solvent is switched to DCM, and the above-mentioned washing process is repeated. After the last DCM wash, the solvent was removed and the Li-UiO-66(MOD) solid was allowed to dry in air. The samples were stored in a desiccator until further use or characterization.
[0088] In other synthesis, instead of TEA, n-butyl lithium is used as alkali.The first synthesized UiO-66 (50Benz) uses the washing procedure described above to exchange from DMF solvent to acetone and then solvent to DCM.Then, 150mg of MOF is placed in the 25mL round-bottomed flask equipped with Schlenk adapter (adapter), and is purged under flowing nitrogen.To this flask, 7mL of 1.6M n-butyl lithium solution in hexane is slowly added to this flask under flowing nitrogen, and keeps continuing 24 hours.Solution is removed, and collected MOF is washed several times with 10mL pentane, then uses distilled tetrahydrofuran soaking and solvent exchange.
[0089] The Li-UiO-66(50Benz) and non-lithiated UiO-66(50Benz) polycrystalline powders at ambient temperature were evaluated by powder X-ray diffraction (PXRD, Bruker D8 Focus diffractometer, Cu Kα, LynxEye detector) and infrared spectroscopy (IR, ThermoScientific Nicolet iS FT-IR with iD 5ATR accessory) with the results in Fig. 9 and Fig.10 Shown in. Fig. 9 and Fig.10 Both show that the lithiated MOFs remain structurally intact and have high crystallinity. Fig. 9 It is shown that for the TEA treated MOF and based on PXRD, the lithiated MOF structure remains intact and has crystallinity compared to the HCl activated UiO-66(50Benz). Fig.10 The asterisk in (IR spectroscopy) shows that UiO-Li has a characteristic MOF carbonyl stretch, indicating that the structure is retained. The slight shift of the Zr-O peak (represented by O) indicates that support node deprotonation occurs. Li-UiO-66 (50Benz) and non-lithiated UiO-66 (50Benz) were further evaluated by scanning electron microscopy (JOEL JSM IT100) and showed no degradation of octahedral crystals or changes in particle size between Li-UiO-66 (50Benz) and UiO-66 (50Benz).
[0090] The chromatographic data were analyzed by thermal imaging (TGA, TA Instruments SDT Q600, at 5.0 °C min -1 The heating rate of Li-UiO-66(50Benz) and UiO-66(50Benz) were further evaluated. Fig.11A and Fig. 11B The TGA curve graph depicted in shows that the characteristic thermal stability of Li-MOF remains unchanged compared with MOF.
[0091] Li-UiO-66(50Benz) and UiO-66(50Benz) were further evaluated by nitrogen adsorption technique (Micromeritics ASAP2020Plus). Li-UiO-66(50Benz) provided 450.6m 2 / g BET surface area, and UiO-66 (50Benz) provides 1520.8m 2 g -1 The BET surface area of the samples was obtained by quantifying the defect concentration. The BET data show that the surface area increases with the defect concentration.
[0092] Therefore, the experimental data indicate that the lithiation process does not degrade the UiO-66 structure and the favorable properties of high crystallinity, thermal stability, and high surface area are retained.
[0093] Example 3: Evaluation of MOF defective site concentration
[0094] Defect site concentration plays a role in lithium storage capacity. Because the increased number of defect sites leads to more acidic protons, the most defective samples will easily undergo H + / Li + exchange, and have a higher lithium content. Based on experimental evidence, it has been shown that the lithium content in Li-UiO-66(noMod), Li-UiO-66(12TFA), and Li-UiO-66(50Benz) increases with increasing defect concentration, as quantified by Li and Zr atomic absorption spectroscopy (AAS, Perkin Elmer AAnalyst 100 system and Perkin Elmer Intesitron hollow cathode lamp). As in Fig.12 As depicted in , the increased amount of defect sites leads to a greater number of acidic protons, and the most defective UiO-66(50Benz) has the greatest lithium incorporation, which also translates to the highest Li atoms per SBU, as shown in Table 2 below. When no base or a weaker base (pyridine) is used in the lithiation procedure, the amount of lithium in the MOF decreases, as shown in Table 3 below. Further based on experimental evidence, it has been found that improved lithiation can be achieved by increasing the temperature or increasing the strength of the base. For example, heating UiO-66(50Benz) in a solution containing LiNO3 and TEA in DMF described above to 60°C (Li-UiO66(50Benz)-60) and 80°C (Li-UiO66(50Benz)-80) resulted in a 1.3-fold and 1.7-fold increase in the molar Li concentration, respectively (see Fig.12and Table 2). Using a stronger base, n-butyllithium (Li-UiO-66(50Benz)-nBuLi), at room temperature also increased the molar Li content by a factor of 1.8 compared to similar room temperature lithiation using TEA. In all cases, the highly lithiated MOFs achieved via these alternative pathways maintained their structural integrity and crystallinity (see Fig. 9 , Fig.10 , Fig.11A and Fig. 11B ).
[0095] Table 2
[0096] Li-UiO samples <![CDATA[Calculated Li atoms per Zr6-SBU]]> Li-UiO-66(noMod) 1.64 Li-UiO-66(12TFA) 1.72 Li-UiO-66(50Benz) 2.25 Li-UiO-66(50Benz)-60 3.03 Li-UiO-66(50Benz)-80 2.85 Li-UiO-66(50Benz)-nBuLi 3.98
[0097] Table 3
[0098] Li-UiO samples Mg Li / g MOF determined by AAA Li-UiO-66(noMod) 7.3 Li-UiO-66(12TFA) 7.8 Li-UiO-66(50Benz) 10.4 Li-UiO-66(50Benz)-Alkali-free 0.6 Li-UiO-66(50Benz)-acid 0.0 Li-UiO-66(50Benz)-pyridine 1.1
[0099] The number and surface area of open sites of UiO-66 (noMod), UiO-66 (50Benz) and MOF-808 were further evaluated. According to the following method, the number of open sites was determined by potentiometric acid-base titration. First, the activated MOF powder was washed with acetone (5x20mL over 24 hours) and vacuumed at 150°C for 2 hours to remove the proton solvent from MOF. Then the vacuumed flask was filled with nitrogen, and about 40mg of powder was placed in a beaker. To this end, a certain volume of 0.01M LiNO3 solution (50mL solution of 50mg MOF) was added to the beaker, the beaker was covered and allowed to stand for at least 16 hours before titration. Potentiometric titration was performed using Vernier LabQuest2 with a pH probe and a drop counter accessory. In order to start titration, the pH of the solution was adjusted by dropwise addition of 0.1M HCl until a pH of 3.00 was reached. The burette was used to titrate at about 0.02mL min -1A 0.05 M NaOH solution was delivered at a rate of 1.5 % to a pH of 11. Following the previously reported procedure, the derivative curves (dpH / dV, where V is the volume of the 0.05 M NaOH solution) were used to determine the equivalence point (EP) to quantify the number of missing linkers for the UiO-66 and MOF-808 samples. The surface area was determined by the Brunauer–Emmett–Teller (BET) method applied to obtain the surface area from the N2 adsorption isotherm. Nitrogen adsorption isotherms (Micromeritics ASAP 2020) for calculation of the BET surface area were collected on samples that had been thoroughly degassed by heat and vacuum at 60°C for 1 hour and then kept at 150°C for 2 hours. The results are reported in Table 4 below. It has been found that the number of open sites can be used to systematically tune the incorporation of guest molecules at the Zr node.
[0100] Table 4
[0101]
[0102]
[0103] Example 4: Cathode and button cell preparation
[0104] Cathode slurry is prepared using 30wt.% MOF, 45wt.% S, 15wt.% Super-P carbon (99+%, Alfa Aesar) and 10wt.% poly (vinylidene fluoride) (PVDF) solid mixture in N-methyl-2-pyrrolidone (NMP). MOF is ground with a mortar and pestle and mixed with sulfur. MOF and sulfur mixture are blended with PVDF and Super-P carbon. Small stainless steel balls are added to the admixture, and the solids are thoroughly mixed using a vortex mixer for 5 minutes. Slurry is prepared by adding NMP to the admixture and homogenizing on a vortex mixer for at least 30 minutes. The amount of NMP is measured by weight, and in some aspects can be 4 times the gross mass of the solid mixture. After initial mixing, more NMP is added as needed to achieve a desired slurry consistency for forming a uniform film after drying. Once homogenized, the slurry was cast onto a pre-weighed 12.7 mm carbon paper disc and dried in an 80° C. oven overnight to form the cathode. The 12.7 mm cathode was weighed again to determine the sulfur loading and stored in an Ar-filled glove box until use.
[0105] CR2032 type button cells were constructed in an Ar filled glove box using a pre-weighed cathode, a polished metal Li anode, two Celgard separators, two stainless steel spacers and a spring (TOB New Energy). Figure 8 The electrolyte consists of 1M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in a mixed solution of 1,2-dimethoxyethane (DME, 99+%) and 1,3-dioxolane (DOL, 99.5%) (1:1, v / v) with 2wt.% lithium nitrate salt (LiNO3, 99%) added. The amount of electrolyte added to each button cell assembly is based on the mass of S on the cathode, with a ratio of 60μL per mg S.
[0106] Example 5: Performance of Li-S cells with cathodes comprising lithiated defective MOFs
[0107] To evaluate the maximum charge capacity and cycle life of Li-S batteries with cathodes comprising lithiated defective MOFs, cathodes containing Li-UiO-66 (MOD) and sulfur / carbon composites were constructed to examine the effects of different lithium contents on the Li-S performance.
[0108] In the evaluation of this example, cyclic voltammetry (CV) was performed on an Ivium-n-STAT multichannel electrochemical analyzer. Freshly prepared button cells were used for CV, where the potential was scanned at 0.1 mV / s relative to Li / Li + The coin cells were cycled between 2.9 V and 1.6 V. The coin cells were cycled galvanostatically after being stationary for 8 h (MNT-BA-5V, MicroNanoTools). Unless otherwise stated, all cells were cycled at C / 10 (168 mA g -1 The battery was cyclically charged and discharged at a C-rate of 100 mA g (where 1 C = fully charged or discharged in 1 hour) for 20 cycles and then at C / 5 (336 mA g -1 S) were charged and discharged for 80 cycles. In order to obtain sufficient statistical significance, at least three of the same batteries were tested under the same conditions.
[0109] Usually, if Fig.13 As shown, a linear trend was observed between the maximum capacity and Li content in the order UiO-66(50Benz), Li-UiO-66(noMod) (“noM-Li”), Li-UiO-66(12TFA), and Li-UiO-66(50Benz). Fig.13 It is also shown that the maximum capacity of Li-MOF obtained from harsh reaction conditions leads to degradation and minimizes Fig.13Specific capacity (mAh g) of the Li-UiO-66(50Benz) cell with the highest Li content evaluated and characterized together with the Li-UiO-66(noMod) cell compared to the UiO-66(50Benz) cell -1 ) and Coulombic efficiency (%) versus battery cycle number, where the first 20 cycles were obtained at a C-rate of C / 10 and the next 20 cycles were obtained at a C-rate of C / 5 (see Fig.14 ). Fig.14 shows that the 918 mAh g -1 Compared with the parent UiO-66 (50Benz), it is as high as 1272mAh g -1 The average maximum (absolute) capacity of the Fig.14 It is also shown that the coulombic efficiency of the lithiated and non-lithiated MOFs is close to 100% during extended cycling. Higher specific capacities are obtained in the lithiated MOFs. It is believed that the increased capacity is indicative of high sulfur utilization and is a direct result of the lithiation of the MOFs. As shown in Fig.14 As observed in the capacity retention shown, the lithiated MOFs show a similar decay rate as the parent UiO-66 sample. MOFs lithiated using higher temperatures and stronger bases generally suffer from poor crystallinity and result in relatively low performance.
[0110] Fig.15A and Fig. 15B It is also shown that Li-UiO-66(50Benz) has better capacity retention than UiO-66(50Benz) when the C-rate changes from C / 10 to 2C and from C / 2 to 4C. The constant current charge-discharge rate (C-rate) reflects the ability of the battery to transport ions and cycle effectively. Both the battery containing Li-UiO-66(50Benz) and the battery containing the UiO-66(50Benz) composite electrode show similar capacity decay in the first five cycles at a slow C-rate of C / 10 ( Fig.15A ). However, differences begin to emerge as the C-rates are sequentially increased, ultimately leading to a 10% improvement in retention when the C-rates reach 1C and 2C. For both the Li-UiO-66(50Benz) and UiO-66(50Benz) cells, the capacity loss is recoverable when returning to the slower C / 10 rate, although with slightly better capacity recovery for the lithiated case. Fig.15A and Fig. 15BThe results in clearly show that the cells containing Li-UiO-66(50Benz) exhibited less capacity decay at each C-rate step in the experiment compared to cells containing non-lithiated UiO-66(50Benz). The ability to deliver charge and maintain capacity over a range of C-rates is an important consideration for meeting the requirements for rapid energy use in a wide range of applications. When the C-rate is further increased beyond 2C, the cells containing lithiated MOFs exhibit significantly improved capacity retention ( Fig. 15B ). The cells containing Li-UiO-66-(50Benz) were able to maintain a stable capacity, with only a 4% drop over 30 cycles at a high rate of 4C. In contrast, the non-lithiated UiO-66(50Benz) cells suffered a significantly worse capacity fade of 12% in the same cycling experiment.
[0111] exist Figure 4A The cycling performance of Li-S cells with LPS-UiO-66(noMod), LPS-UiO-66(50Benz), and UiO-66 compared with S / C composite cathodes (45 wt% S / C) is shown in Figure 2. The LPS-MOF composite cathodes produced significantly higher maximum capacities than similar MOF electrodes, with an average of 1193 mAh g for LPS-UiO-66(50Benz), LPS-UiO-66(noMod), and UiO-66, respectively. -1 , 1172mAh g -1 and 891mAh g -1 (See also Fig.16A The increase in maximum capacity is consistent with the increased lithium content measured by atomic absorption spectroscopy (AAS) (see Table 5 below), indicating that increasing LPS loading improves sulfur utilization. In addition to the improved utilization, cells constructed with LPS-UiO-66(noMod) and LPS-UiO-66(50Benz) show greater capacity retention than UiO-66(50Benz). After 100 cycles (20x C / 10, 80x C / 5), only 560 mAh g -1 In comparison, the LPS-UiO-66(50Benz) and LPS-UiO-66(noMod) composite cathodes have 835 mAh g -1 and 767mAh g -1 The average specific capacity ( Figure 4A and Fig. 16B ).
[0112] MOF-808 has more open sites than UiO-66, enhancing its ability to bind additional equivalents of thiophosphate. Based on the results for LPS-UiO-66, it is believed that both the maximum capacity and capacity retention increase with increasing LPS concentration without being bound to any particular theory. Composite cathodes of LPS-MOF-808 samples synthesized using 0.7, 1.0, and 2.0 LPS equivalents per Zr were assembled into cells and cycled galvanostatically using the same procedure as the LPS-UiO-66 samples ( Figure 4B and Fig. 16B ). Fig.16A The compiled results in show a clear trend of maximum capacity delivery, where the 0.7x-LPS-MOF-808 sample, the 1.0x-LPS-MOF-808 sample, and the 2.0x-LPS-MOF-808 sample have ~70 mAh g -1 , 130mAh g -1 and 300mAh g -1 The increased capacity is again attributed to the increased Li content and LPS content in the functionalized MOF. After 100 cycles, the capacity retention is similar to that of LPS-UiO-66, with 0.7x-LPS-MOF-808 cells, 1.0x-LPS-MOF-808 cells, and 2.0x-LPS-MOF-808 cells delivering ∼800 mAh g -1 The capacity of the battery containing MOF-808 is less than 700 mAh g -1 Furthermore, all cells constructed with LPS-MOF additives exhibited higher capacity retention when compared to sulfur-carbon composite cathodes (45 wt% S / C). Figure 4A , Figure 4B , Fig.16A and Fig. 16B ).
[0113] The performance of LPS-MOF composite cells was evaluated under more difficult cycling conditions. Compared with UiO-66(50Benz), LPS-UiO-66(50Benz) composite cells exhibited higher capacity at all C-rates ( Fig.17A and Fig. 17B ). Moreover, when returning to a lower C-rate of C / 10, the LPS-UiO-66(50Benz) cell surprisingly recovered and maintained ∼1040 mAh g -1, which is the same capacity as it had after the first 5 cycles at C / 10. In contrast, the UiO-66(50Benz) and 45wt% S / C cells do not fully recover capacity and continue to experience capacity fade, losing almost 200mAh g in just 15 cycles. -1 This superior ability of LPS-UiO-66(50Benz) to recover capacity is evident even after the cells have been abused by continuous cycling at charge rates up to 4C and prolonged storage in a discharged state. When the C-rate is slowed to C / 10 after these severe cycling conditions, the LPS-LPS-UiO-66(50Benz) cells deliver 940 mAh g -1 The capacity of UiO-66 (50Benz) battery can only reach 250mAh g -1 , and the 45wt% S / C cell irreversibly decayed to zero capacity. The cell constructed with the LPS-MOF composite cathode also showed improved capacity delivery and retention in long-term cycling experiments at a C-rate of 1C ( Fig.18 ). Fig.18 It is also shown that the coulombic efficiency of the lithiated and non-lithiated MOFs is close to 100% during extended cycling. It is surprising to find that the LPS-UiO-66(50Benz) and LPS-UiO-66(noMod) composite cathodes deliver ∼375 mAh g-1 after 600 cycles, respectively. -1 and ~300mAh g -1 , while the 45wt% S / C battery cannot even maintain 100mAhg -1 .
[0114] Example 6: Preparation of defective MOFs with chemical anchors
[0115] The thiophosphate / root precursor Li3PS4 was synthesized by mixing 200 mg of P2S5 (0.9 mmol) with 122 mg of Li2S (2.7 mmol) in a 20 mL scintillation vial in an Ar-filled glove box. 5 mL of distilled THF was added to these solids and stirred at room temperature in the glove box for 24 hours. A yellow solution and a white powder were obtained after the reaction mixture was allowed to settle. The yellow solution was removed and the solids were washed successively with THF until the yellow color was no longer observed. Additional THF was used to suspend the powder and transfer the product to a 50 mL recovery flask equipped with a Schlenk connector. The sealed flask was then removed from the glove box and evacuated at room temperature for 3 hours, followed by another evacuation at 140 ° C for 8 hours. The flask was brought back to the glove box and produced 284 mg of product (yield = 88%). Solution in 1M NaOH in D2O 31P-NMR (Bruker Avance 400MHz spectrometer) with PS4 3- The substance produced a single peak at δ=87 ppm.
[0116] UiO-66 (MOD) was prepared and activated according to the method of Example 1.
[0117] Phosphate moieties can be incorporated into the UiO-66 (MOD) moiety via solvent-assisted ligand incorporation, where the activated MOF is soaked in a solution of the desired phosphate or phosphonate compound. In this example, the solvent was selected so as to preserve the oxidation-sensitive thiophosphate species. The amount of Li3PS4 used to prepare the LPS precursor solution varied for different MOF loadings. For all UiO-66 MOFs, the same mass ratio of 3:1 (UiO-66:Li3PS4) was used. This ratio is selected if the molar mass of the UiO-66 used is a highly defective "reo" phase or a parent defect-free structure, as it falls within the PS4 required to fully occupy the missing linker open sites. 3- In calculations for defective or defect-free structures, a value of 3 open sites per mole of MOF was used to overestimate the amount of Li3PS4 required.
[0118] The calculated mass of Li3PS4 is placed in a flask in a glove box filled with Ar and covered with a rubber septum. The LPS precursor solution is prepared using a dry triethylamine-methanol solution mixed in a 1:4 (v:v) ratio. The solution is used to dissolve the Li3PS4 salt under an inert atmosphere to form an approximate Li3PS4 molar concentration of ~50mM. Once dissolved, the LPS precursor solution is injected into a flask containing the activated MOF at room temperature under an inert atmosphere. The flask is sealed, rotated and then left undisturbed for 24 hours. The color of the MOF powder remains unchanged during this loading procedure.
[0119] After 24 hours of soaking, the liquid phase was replaced with 8mL of dry THF, and soaking was allowed to continue for a minimum of 24 hours. The THF washing procedure was repeated over the course of 3 days (5x 8mL THF) and was always maintained under an inert atmosphere. The last THF washing solution was removed, and the sample was dried in a vacuum at room temperature for 3 hours. The resulting MOF-LPS powder (defective MOF functionalized with ca chemical anchors) was returned to the glove box for storage and future use. Based on this method, typically, approximately 70%-80% of the initial mass of the unactivated MOF used is recovered after LPS loading. Figure 5A Transmittance (%) versus wavenumber (cm2) of LPS-functionalized UiO-66 (50Benz) and the parent defect-free MOF (UiO-66) are plotted.-1 ) infrared (IR) spectrum results, Figure 5B Transmittance (%) versus wavenumber (cm2) of LPS-functionalized MOF-808 and the parent defect-free MOF (MOF-808) are plotted. -1 )’s infrared (IR) spectrum results. Fig. 7A and Figure 7B Depicted is the LPS-functionalized UiO-66(50Benz)( Fig. 7A ) and LPS-functionalized MOF-808 ( Figure 7B ) in the solid state magic angle spin 31 P NMR (solid-state magic-anglespinning 31 P Nuclear Magnetic Resonance) (NMR, AVIII 500 MHz spectrometer with standard Bruker 4 mm HX probe, 15 kHz spinning speed) spectroscopy.
[0120] Solid-state morphology of LPS-functionalized UiO-66(50Benz) and LPS-functionalized MOF-808 by digestion in aqueous 1 M NaOH overnight to digest the MOF and release the incorporated guest molecules 31 P solution NMR spectroscopy to confirm the successful incorporation of the thiophosphate species. If LPS-UiO-66(50Benz) is digested, 31 The P solution NMR spectrum showed a single peak at 91.7 ppm, which was attributed to Li4P2S7 (see Figure 6 ).
[0121] The defective MOF-808 with chemical anchors was prepared as follows. In a 500 mL screw-cap glass container, a solution of H3BTC (1 g, 5 mmol) and ZrOCl2·8H2O (5 g, 15 mmol) dissolved in 1:1 DMF / HCOOH (450 mL) was heated at 130 °C for 2 days. The white solid was separated and washed 5 times with DMF, 5 times with H2O, and 5 times with acetone over 3 consecutive days. The solid was filtered and air-dried for 24 hours. The activated sample was additionally heated at 150 °C under vacuum for 24 hours. Then, using a stoichiometric amount of Li3PS4 considering the starting mass of MOF-808, the activated MOF was treated with a solution of LPS in trimethylamine and methanol (1:4 v / v). The loading and washing procedures were consistent with those used for preparing LPS-functionalized UiO-66 (above). According to the current example, the stoichiometry of LPS with MOF-808 was varied. MOF-808 has 6 open sites on its Zr nodes. Thus, theoretically, 6 moles of Li3PS4 are required per mole of MOF-808 to derivatize chemical anchors at each open site, and such an LPS MOF-808 will be referred to as 1xLPS MOF-808. Similarly, an LPS MOF-808 prepared with 4.2 moles of Li3PS4 per mole of MOF-808 will be referred to as 0.7xLPS MOF-808, and an LPS MOF-808 prepared with 12 moles of Li3PS4 per mole of MOF-808 will be referred to as 2xLPS MOF-808.
[0122] It has been found that the thiophosphate loading can be controlled while maintaining the MOF structure. Elemental analysis shows that the degree of LPS loading is directly related to the number of open sites. The digested samples showed increasing Li and P contents in the order of UiO-66(noMod) < UiO-66(50Benz) < MOF-808, as shown in Table 5 below. In Table 5: "AAS" refers to atomic absorption spectroscopy obtained using a Perkin Elmer AAnalyst 100 system and a Perkin Elmer Intesitron hollow cathode lamp; "ICP-OES" refers to inductively coupled plasma optical emission spectroscopy; and "EDS" refers to energy-dispersive X-ray spectroscopy collected using a JEOL JSM IT100 scanning electron microscope. Due to its larger pore size and higher number of open sites, MOF-808 can incorporate additional LPS units when the loading ratio of LPS to Zr increases from 0.7 to 2. The successful incorporation of the thiophosphate species was further confirmed by solution-state 31 31P NMR spectroscopy.
[0123] Table 5
[0124]
[0125] This written description uses examples to disclose the invention, including the best mode, and also to enable any person skilled in the art to practice the invention, including making and using any devices or systems and performing any incorporated methods. The patentable scope of the invention is defined by the claims, and may include other examples that occur to those skilled in the art. Such other examples are intended to be within the scope of the claims if they have structural elements that do not differ from the literal language of the claims or if they include equivalent structural elements with insubstantial differences from the literal language of the claims.
[0126] This article also provides the following items:
[0127] 1. A battery cathode comprising a plurality of defective metal organic framework portions:
[0128] (i) wherein each defective metal-organic framework portion independently comprises at least one defect selected from structural defects and compositional features; and
[0129] (ii) wherein each defect independently allows for the capture of battery anode metal ions, incorporates a chemical anchor substituent for the capture of polysulfides, or a combination thereof.
[0130] 2. A battery cathode according to item 1, wherein the defective metal organic framework portion differs from the parent metal organic framework portion in terms of the presence of the defects.
[0131] 3. A battery cathode according to item 1 or item 2, wherein the metal of the metal organic framework is selected from zirconium, hafnium, cesium, copper, zinc, titanium, iron, vanadium, molybdenum, niobium and chromium.
[0132] 4. A battery cathode according to any one of items 1 to 3, wherein the metal of the metal organic framework is zirconium.
[0133] 5. The battery cathode according to any one of items 1 to 4, wherein the defects are independently selected from metal coordination sites and proton sites.
[0134] 6. A battery cathode according to item 5, wherein a portion of the plurality of defective metal-organic framework portions comprises at least one defect, wherein the at least one defect is a proton site.
[0135] 7. The battery cathode according to item 6, wherein each proton site is independently selected from a hydroxyl group and a water group.
[0136] 8. A battery cathode according to any one of items 1 to 7, wherein the cathode comprises sulfur and is a lithium-sulfur battery cathode.
[0137] 9. A battery cathode according to any one of items 6 to 8, wherein a substantial portion of the proton sites are functionalized with lithium.
[0138] 10. A battery cathode according to any one of items 1 to 7, wherein the cathode comprises sulfur and is a sodium-sulfur battery cathode.
[0139] 11. The battery cathode of item 10, wherein a substantial portion of the proton sites are sodium functionalized.
[0140] 12. A battery cathode according to any one of items 1 to 5, wherein a portion of the plurality of defective metal-organic framework portions comprises metal coordination sites, chemical anchor substituents functionalized to proton sites for capturing polysulfides, or a combination thereof.
[0141] 13. A battery cathode according to item 12, wherein a portion of the plurality of defective metal organic framework portions comprises a chemical anchor substituent selected from thiophosphate, thiogermanate and thioarsenate.
[0142] 14. A battery cathode according to item 13, wherein the chemical anchor substituent is a thiophosphate.
[0143] 15. A battery cathode according to any one of items 1 to 4, comprising a combination of a metal organic framework comprising the defects of item 8 or 9 or the defects of item 10 or 11 and a metal organic framework comprising the defects of any one of items 12 to 14.
[0144] 16. A lithium-sulfur battery comprising:
[0145] (i) an anode comprising lithium;
[0146] (ii) electrolyte; and
[0147] (iii) a cathode comprising sulfur and a plurality of defective metal organic framework portions, wherein:
[0148] (1) wherein each defective metal-organic framework portion independently comprises at least one defect selected from structural defects and compositional features; and
[0149] (2) Each defect independently allows for the capture of battery anode metal ions or incorporates chemical anchor substituents for the capture of polysulfides.
[0150] 17. The lithium-sulfur battery according to item 16, wherein the defective metal-organic framework portion differs from the parent metal-organic framework portion in the presence of the defects.
[0151] 18. The lithium-sulfur battery according to item 16 or item 17, wherein the metal of the metal organic framework is selected from zirconium, hafnium, cesium, copper, zinc, titanium, iron, vanadium, molybdenum, niobium and chromium.
[0152] 19. The lithium-sulfur battery according to item 18, wherein the metal of the metal organic framework is zirconium.
[0153] 20. A lithium-sulfur battery according to any one of items 16 to 19, wherein the defects are independently selected from metal coordination sites and proton sites.
[0154] 21. The lithium-sulfur battery of any one of items 16 to 20, wherein a portion of the plurality of defective metal-organic framework portions comprises at least one defect, the at least one defect being a proton site.
[0155] 22. The lithium-sulfur battery according to item 21, wherein each proton site is independently selected from a hydroxyl group and a water group.
[0156] 23. A lithium-sulfur battery according to item 21 or item 22, wherein a substantial portion of the proton sites are functionalized with lithium.
[0157] 24. A lithium-sulfur battery according to any one of items 16 to 20, wherein a portion of the plurality of defective metal-organic framework portions comprises defects that are metal coordination sites, defects that are chemical anchor substituents functionalized to the proton sites for capturing polysulfides, or a combination thereof.
[0158] 25. The lithium-sulfur battery according to item 24, wherein the chemical anchor substituent is selected from thiophosphate, thiogermanate and thioarsenate.
[0159] 26. The lithium-sulfur battery according to item 25, wherein the chemical anchor is thiophosphate.
[0160] 27. A lithium-sulfur battery according to any one of items 16 to 20, wherein the cathode comprises a combination of a metal organic framework comprising the defects of any one of items 21 to 23 and a metal organic framework comprising the defects of any one of items 24 to 26.
[0161] 28. The lithium-sulfur battery according to any one of items 16 to 27, which has a capacity retention of at least 60%, at least 65%, at least 70%, at least 75% or at least 80% after 20 charge-discharge cycles.
[0162] 29. A lithium-sulfur battery according to any one of items 16 to 28, having a capacity of at least 800 mAh g after 20 charge-discharge cycles. -1 , at least 900mAh g -1 , at least 1000mAh g -1 , at least 1100mAh g -1 or at least 1200mAh g -1 absolute capacity.
[0163] 30. A solid material having lithium conductivity, the material comprising lithium and a plurality of defective metal organic framework portions:
[0164] (i) wherein each defective metal organic framework portion independently comprises a defect selected from a metal coordination site, a compositional feature, and a proton site; and
[0165] (ii) wherein the lithium is bound to or trapped by the defects.
[0166] 31. A solid material according to item 30, wherein the defective metal-organic framework portion differs from the parent metal-organic framework portion in terms of the presence of the defects.
[0167] 32. A solid material according to item 30 or item 31, wherein the metal of the metal organic framework is selected from zirconium, hafnium, cesium, copper, zinc, titanium, iron, vanadium, molybdenum, niobium and chromium.
[0168] 33. A solid material according to item 32, wherein the metal is zirconium.
[0169] 34. A solid material according to any one of items 30 to 33, wherein a portion of the plurality of defective metal-organic framework portions comprises at least one defect, the at least one defect being a proton site.
[0170] 35. A solid material according to item 34, wherein each proton site is independently selected from a hydroxyl group and a water group.
[0171] 36. A solid material according to any one of items 30 to 35, wherein the solid material is an electrolyte.
[0172] 37. A method of using a lithium-sulfur battery, the method comprising:
[0173] (i) providing a lithium-sulfur battery having a charge cycle and a discharge cycle, wherein
[0174] (1) The lithium-sulfur battery comprises:
[0175] (a) an anode comprising lithium,
[0176] (b) electrolyte, and
[0177] (c) a cathode comprising sulfur and a plurality of defective metal organic framework portions comprising at least one defect selected from structural defects and compositional features, wherein each defect independently allows for the capture of lithium ions;
[0178] (2) the discharge cycle comprises reducing elemental sulfur and / or lithium polysulfide to lithium sulfide at the cathode, wherein at least a portion of the lithium polysulfide is partially captured by the defective metal-organic framework;
[0179] (3) the charge cycle comprises oxidation of lithium sulfide at the cathode to lithium polysulfide and / or elemental sulfur, wherein at least a portion of the lithium polysulfide in the oxidation reaction is the lithium polysulfide captured during the discharge cycle;
[0180] (ii) providing a lithium-sulfur battery having a charge cycle and a discharge cycle, wherein
[0181] (1) The lithium-sulfur battery comprises:
[0182] (a) an anode comprising lithium,
[0183] (b) electrolyte, and
[0184] (c) a cathode comprising sulfur and a plurality of defective metal organic framework portions comprising at least one defect selected from a metal coordination site and a chemical anchor substituent capable of functionalizing a polysulfide thereto;
[0185] (2) the discharge cycle comprises reducing elemental sulfur and / or lithium polysulfide to lithium sulfide at the cathode, wherein at least a portion of the polysulfide is captured into metal organic framework chemical anchor sites by functionalization; and
[0186] (3) the charge cycle comprises oxidation of lithium sulfide at the cathode to lithium polysulfide and / or elemental sulfur, wherein at least a portion of the lithium polysulfide in the oxidation reaction is the lithium polysulfide captured during the discharge cycle; or
[0187] (iii) providing a lithium-sulfur battery having a charge cycle and a discharge cycle, wherein
[0188] (1) The lithium-sulfur battery comprises:
[0189] (a) an anode comprising lithium,
[0190] (b) electrolyte, and
[0191] (c) a cathode comprising sulfur and (I) a plurality of defective metal organic framework portions comprising at least one defect selected from structural defects and compositional features, wherein each defect independently allows for the capture of lithium ions, and (II) a plurality of defective metal organic framework portions comprising at least one defect selected from metal coordination sites and chemical anchor substituents capable of functionalizing polysulfides thereto;
[0192] (2) the discharge cycle comprises reducing elemental sulfur and / or lithium polysulfide to lithium sulfide at the cathode, wherein at least a portion of the lithium polysulfide is captured into metal organic framework chemical anchor sites by functionalization; and
[0193] (3) The charge cycle comprises oxidation of lithium sulfide to lithium polysulfide and / or elemental sulfur at the cathode, wherein at least a portion of the lithium polysulfide in the oxidation reaction is the lithium polysulfide captured during the discharge cycle.
[0194] 38. The method of item 37, wherein the defective metal organic framework portion differs from the parent metal organic framework portion in the presence of the defects.
[0195] 39. The method according to item 37 or item 38, wherein the metal of the metal organic framework is selected from zirconium, hafnium, cesium, copper, zinc, titanium, iron, vanadium, molybdenum, niobium and chromium.
[0196] 40. The method according to item 39, wherein the metal is zirconium.
[0197] 41. The method according to any one of items 37 to 40, comprising:
[0198] (i) a defective metal organic framework portion of the cathode of step (i)(1)(c) and step (iii)(1)(c)(I) of item 37, wherein the defective metal organic framework portion of the plurality of defective metal organic framework portions independently comprises one or more defects selected from dislocation structural defects, local structural defects, large-scale structural defects, metal coordination sites and proton sites, wherein the defects are capable of capturing lithium; and
[0199] (ii) a defective metal organic framework portion of the cathode of step (ii)(1)(c) and step (ii)(1)(c)(II) of item 37, wherein the defective metal organic framework comprises one or more defects selected from metal coordination sites and chemical anchor substituents capable of functionalizing polysulfide thereto.
[0200] 42. A method according to any one of items 37 to 41, wherein a portion of the multiple defective metal-organic framework portions of the cathode in step (i)(1)(c) and step (iii)(1)(c)(I) of item 37 includes at least one defect, and the at least one defect is a proton site.
[0201] 43. The method according to item 42, wherein each proton site is independently selected from a hydroxyl group and a water group.
[0202] 44. A method according to any one of items 37 to 41, wherein a portion of the multiple defective metal-organic framework portions of the cathode in step (i)(1)(c) and step (iii)(1)(c)(II) of item 37 independently includes at least one defect selected from a metal coordination site, a chemical anchor substituent for capturing polysulfides, or a combination thereof.
[0203] 45. The method according to item 44, wherein the defect is a chemical anchor substituent, which is functionalized to a proton site and is selected from thiophosphate, thiogermanate and thioarsenate.
[0204] 46. A method according to item 45, wherein the chemical anchor is thiophosphate.
[0205] 47. A method according to any one of items 37 to 46, wherein the lithium-sulfur battery has a capacity retention of at least 60%, at least 65%, at least 70%, at least 75% or at least 80% after 20 charge-discharge cycles.
[0206] 48. A method according to any one of items 37 to 47, wherein the lithium-sulfur battery has a capacity of at least 800 mAh g after 20 charge-discharge cycles. -1 , at least 900mAh g -1 , at least 1000mAh g -1 , at least 1100mAh g -1 or at least 1200mAh g -1 absolute capacity.
[0207] 49. An ambient temperature sodium-sulfur battery comprising:
[0208] (i) an anode comprising sodium;
[0209] (ii) electrolyte; and
[0210] (iii) a cathode comprising sulfur and a plurality of defective metal organic framework portions, wherein:
[0211] (1) wherein each defective metal-organic framework portion independently comprises at least one defect selected from structural defects and compositional features; and
[0212] (2) Each defect independently allows for the capture of battery anode metal ions or incorporates chemical anchor substituents for the capture of polysulfides.
[0213] 50. The sodium-sulfur battery of item 49, wherein the defective metal-organic framework portion differs from the parent metal-organic framework portion in the presence of the defects.
[0214] 51. A sodium-sulfur battery according to item 49 or item 50, wherein the metal of the metal organic framework is selected from zirconium, hafnium, cesium, copper, zinc, titanium, iron, vanadium, molybdenum, niobium and chromium.
[0215] 52. A sodium-sulfur battery according to item 51, wherein the metal of the metal organic framework is zirconium.
[0216] 53. A sodium-sulfur battery according to any one of items 49 to 52, wherein the defects are independently selected from metal coordination sites and proton sites.
[0217] 54. A sodium-sulfur battery according to any one of items 49 to 53, wherein a portion of the plurality of defective metal-organic framework portions comprises at least one defect, the at least one defect being a proton site.
[0218] 55. The sodium-sulfur battery according to item 54, wherein each proton site is independently selected from a hydroxyl group and a water group.
[0219] 56. A sodium-sulfur battery according to item 54 or item 55, wherein a substantial portion of the proton sites are functionalized with sodium.
[0220] 57. A sodium-sulfur battery according to any one of items 49 to 53, wherein a portion of the plurality of defective metal-organic framework portions comprises defects that are metal coordination sites, defects that are chemical anchor substituents functionalized to the proton sites for capturing polysulfides, or a combination thereof.
[0221] 58. A sodium-sulfur battery according to item 57, wherein the chemical anchor substituent is selected from thiophosphate, thiogermanate and thioarsenate.
[0222] 59. The sodium-sulfur battery according to item 58, wherein the chemical anchor is thiophosphate.
[0223] 60. A sodium-sulfur battery according to any one of items 49 to 53, wherein the cathode comprises a combination of a metal organic framework comprising the defects of any one of items 54 to 56 and a metal organic framework comprising the defects of any one of items 57 to 59.
[0224] 61. A solid material having sodium conductivity, the material comprising sodium and a plurality of defective metal organic framework portions:
[0225] (i) wherein each defective metal organic framework portion independently comprises a defect selected from a metal coordination site, a compositional feature, and a proton site; and
[0226] (ii) wherein the sodium is bound to or trapped by the defect.
[0227] 62. A solid material according to item 61, wherein the defective metal-organic framework portion differs from the parent metal-organic framework portion in terms of the presence of the defects.
[0228] 63. A solid material according to item 61 or item 62, wherein the metal of the metal organic framework is selected from zirconium, hafnium, cesium, copper, zinc, titanium, iron, vanadium, molybdenum, niobium and chromium.
[0229] 64. A solid material according to item 63, wherein the metal is zirconium.
[0230] 65. A solid material according to any one of items 61 to 64, wherein a portion of the plurality of defective metal-organic framework portions comprises at least one defect, the at least one defect being a proton site.
[0231] 66. A solid material according to item 65, wherein each proton site is independently selected from a hydroxyl group and a water group.
[0232] 67. A solid material according to any one of items 61 to 66, wherein the solid material is an electrolyte.
[0233] 68. A method of using an ambient temperature sodium-sulfur battery, the method comprising:
[0234] (i) providing an ambient temperature sodium-sulfur battery, the battery having a charge cycle and a discharge cycle, wherein
[0235] (1) The sodium-sulfur battery comprises:
[0236] (a) an anode comprising sodium,
[0237] (b) electrolyte, and
[0238] (c) a cathode comprising sulfur and a plurality of defective metal organic framework portions comprising at least one defect selected from structural defects and compositional features, wherein each defect independently allows for the capture of sodium ions;
[0239] (2) the discharge cycle comprises reducing elemental sulfur and / or sodium polysulfide to sodium sulfide at the cathode, wherein at least a portion of the sodium polysulfide is partially captured by the defective metal-organic framework;
[0240] (3) the charging cycle comprises oxidizing sodium sulfide at the cathode to sodium polysulfide and / or elemental sulfur, wherein at least a portion of the sodium polysulfide in the oxidation reaction is the sodium polysulfide captured in the discharging cycle;
[0241] (ii) providing an ambient temperature sodium-sulfur battery, the battery having a charge cycle and a discharge cycle, wherein
[0242] (1) The sodium-sulfur battery comprises:
[0243] (a) an anode comprising sodium,
[0244] (b) electrolyte, and
[0245] (c) a cathode comprising sulfur and a plurality of defective metal organic framework portions comprising at least one defect selected from a metal coordination site and a chemical anchor substituent capable of functionalizing a polysulfide thereto;
[0246] (3) the discharge cycle comprises reducing elemental sulfur and / or sodium polysulfide to sodium sulfide at the cathode, wherein at least a portion of the polysulfide is captured by functionalization into metal organic framework chemical anchor sites; and
[0247] (4) the charging cycle comprises oxidation of sodium sulfide to sodium polysulfide and / or elemental sulfur at the cathode, wherein at least a portion of the sodium polysulfide in the oxidation reaction is the sodium polysulfide captured in the discharging cycle; or
[0248] (iii) providing an ambient temperature sodium-sulfur battery, the battery having a charge cycle and a discharge cycle, wherein
[0249] (1) The sodium-sulfur battery comprises:
[0250] (a) an anode comprising sodium,
[0251] (b) electrolyte, and
[0252] (c) a cathode comprising sulfur and (I) a plurality of defective metal organic framework portions comprising at least one defect selected from structural defects and compositional features, wherein each defect independently allows for the capture of sodium ions, and (II) a plurality of defective metal organic framework portions comprising at least one defect selected from metal coordination sites and chemical anchor substituents capable of functionalizing polysulfides thereto;
[0253] (2) the discharge cycle comprises reducing elemental sulfur and / or sodium polysulfide to sodium sulfide at the cathode, wherein at least a portion of the sodium polysulfide is captured into metal organic framework chemical anchor sites by functionalization; and
[0254] (3) The charge cycle includes oxidizing sodium sulfide to sodium polysulfide and / or elemental sulfur at the cathode, wherein at least a portion of the sodium polysulfide in the oxidation reaction is the sodium polysulfide captured in the discharge cycle.
[0255] 69. A method according to item 68, wherein the defective metal organic framework portion differs from the parent metal organic framework portion in the presence of the defects.
[0256] 70. The method according to item 68 or item 69, wherein the metal of the metal organic framework is selected from zirconium, hafnium, cesium, copper, zinc, titanium, iron, vanadium, molybdenum, niobium and chromium.
[0257] 71. The method according to item 70, wherein the metal is zirconium.
[0258] 72. The method according to any one of items 68 to 71, comprising:
[0259] (i) a defective metal organic framework portion of the cathode of step (i)(1)(c) and step (iii)(1)(c)(I) of item 68, wherein the defective metal organic framework portion of the plurality of defective metal organic framework portions independently comprises one or more defects selected from dislocation structural defects, local structural defects, large-scale structural defects, metal coordination sites and proton sites, wherein the defects are capable of capturing sodium; and
[0260] (ii) a defective metal organic framework portion of the cathode of step (ii)(1)(c) and step (ii)(1)(c)(II) of item 68, wherein the defective metal organic framework comprises one or more defects selected from metal coordination sites and chemical anchor substituents capable of functionalizing polysulfide thereto.
[0261] 73. A method according to any one of items 68 to 72, wherein a portion of the multiple defective metal-organic framework portions of the cathode in step (i)(1)(c) and step (iii)(1)(c)(I) of item 68 includes at least one defect, and the at least one defect is a proton site.
[0262] 74. The method of item 73, wherein each proton site is independently selected from a hydroxyl group and a water group.
[0263] 75. A method according to any one of items 68 to 72, wherein a portion of the multiple defective metal-organic framework portions of the cathode in step (i)(1)(c) and step (iii)(1)(c)(II) of item 68 independently includes at least one defect selected from a metal coordination site, a chemical anchor substituent for capturing polysulfides, or a combination thereof.
[0264] 76. A method according to item 75, wherein the defect is a chemical anchor substituent, which is functionalized to a proton site and is selected from thiophosphate, thiogermanate and thioarsenate.
[0265] 77. A method according to item 76, wherein the chemical anchor is thiophosphate.
Claims
1. A lithium-sulfur or sodium-sulfur battery cathode, the battery cathode comprising a plurality of defective metal organic framework portions: (i) wherein each defective metal organic framework portion independently comprises at least one defect independently selected from a metal coordination site and a proton site; and (ii) wherein each defect independently allows for the capture of battery anode metal ions, functionalized chemical anchor substituents for the capture of polysulfides, or a combination thereof, The metal of the metal organic framework part is selected from zirconium, hafnium, cesium, copper, zinc, titanium, iron, vanadium, molybdenum, niobium and chromium.
2. The battery cathode of claim 1, wherein the defective metal organic framework portion differs from a parent metal organic framework portion in the presence of the defects.
3. The battery cathode of claim 1, wherein the metal of the metal organic framework portion is zirconium.
4. The battery cathode of claim 1, wherein a portion of the plurality of defective metal organic framework portions comprises at least one defect, the at least one defect being a proton site.
5. The battery cathode of claim 1, wherein each proton site is independently selected from a hydroxyl group and a H2O group.
6. The battery cathode of claim 1, wherein the battery cathode comprises sulfur and is a lithium-sulfur battery cathode.
7. The battery cathode of claim 6, wherein a portion of the proton sites are functionalized with lithium.
8. The battery cathode of claim 1, wherein the battery cathode comprises sulfur and is a sodium-sulfur battery cathode.
9. The battery cathode of claim 8, wherein a portion of the proton sites are functionalized with sodium.
10. The battery cathode of any one of claims 1 to 3, wherein a portion of the plurality of defective metal organic framework portions comprises metal coordination sites, chemical anchor substituents functionalized to proton sites for capturing polysulfides, or a combination thereof.
11. The battery cathode of claim 10, wherein the chemical anchor substituent is selected from thiophosphate, thiogermanate, and thioarsenate.
12. The battery cathode of claim 11, wherein the chemical anchor substituent is a thiophosphate.
13. A battery cathode according to any one of claims 1 to 3, comprising a combination of a metal organic framework comprising defects as defined in claim 7 or defects as defined in claim 9 and a metal organic framework comprising defects as defined in claim 11 or claim 12.
14. A lithium-sulfur battery comprising: (i) an anode comprising lithium; (ii) electrolyte; as well as (iii) a cathode comprising sulfur and a plurality of defective metal organic framework portions, wherein: (1) wherein each defective metal organic framework portion independently comprises at least one defect independently selected from a metal coordination site and a proton site; and (2) wherein each defect independently allows for the capture of battery anode metal ions or is functionalized as a chemical anchor substituent for the capture of polysulfides, The metal of the metal organic framework part is selected from zirconium, hafnium, cesium, copper, zinc, titanium, iron, vanadium, molybdenum, niobium and chromium.
15. The lithium-sulfur battery of claim 14, wherein the defective metal organic framework portion differs from a parent metal organic framework portion in the presence of the defects.
16. The lithium-sulfur battery of claim 14, wherein the metal of the metal organic framework part is zirconium.
17. The lithium-sulfur battery of claim 14, wherein a portion of the plurality of defective metal-organic framework portions comprises at least one defect, the at least one defect being a proton site.
18. The lithium-sulfur battery of claim 17, wherein each proton site is independently selected from a hydroxyl group and a H2O group.
19. A lithium-sulphur battery according to claim 17 or claim 18, wherein a portion of the proton sites are functionalised with lithium.
20. The lithium-sulfur battery of any one of claims 14 to 16, wherein a portion of the plurality of defective metal organic framework portions comprises defects that are metal coordination sites, defects that are chemical anchor substituents functionalized to the proton sites for capturing polysulfides, or a combination thereof.
21. The lithium-sulfur battery of claim 20, wherein the chemical anchor substituent is selected from thiophosphate, thiogermanate, and thioarsenate.
22. The lithium-sulfur battery of claim 21, wherein the chemical anchor substituent is a thiophosphate.
23. The lithium-sulfur battery according to any one of claims 14 to 16, wherein the cathode comprises a combination of a metal organic framework comprising defects as defined in any one of claims 17 to 18 and a metal organic framework comprising defects as defined in any one of claims 21 to 22.
24. The lithium-sulfur battery of any one of claims 14 to 18, having a capacity retention of at least 60% after 20 charge-discharge cycles.
25. A lithium-sulfur battery according to any one of claims 14 to 18 having a capacity of at least 800 mAh g after 20 charge-discharge cycles. -1 absolute capacity.
26. A solid material having lithium conductivity, the solid material comprising lithium and a plurality of defective metal organic framework portions: (i) wherein each defective metal organic framework portion independently comprises a defect selected from a metal coordination site and a proton site; and (ii) wherein the lithium is bound to or trapped by the defect, The metal of the metal organic framework part is selected from zirconium, hafnium, cesium, copper, zinc, titanium, iron, vanadium, molybdenum, niobium and chromium.
27. The solid material of claim 26, wherein the defective metal organic framework portion differs from a parent metal organic framework portion in the presence of the defects.
28. The solid material of claim 26, wherein the metal is zirconium.
29. The solid material of claim 26, wherein a portion of the plurality of defective metal organic framework portions comprises at least one defect, the at least one defect being a proton site.
30. The solid material of claim 26, wherein each proton site is independently selected from a hydroxyl group and a H2O group.
31. A solid material according to any one of claims 26 to 30, wherein the solid material is an electrolyte.
32. A method of using a lithium-sulfur battery, the method comprising: (i) providing a lithium-sulfur battery having a charge cycle and a discharge cycle, wherein (1) The lithium-sulfur battery comprises: (a) an anode comprising lithium, (b) electrolyte, and (c) a cathode comprising sulfur and a plurality of defective metal organic framework portions comprising at least one defect independently selected from a metal coordination site and a proton site, wherein each defect independently allows for the capture of lithium ions; (2) the discharge cycle comprises reducing elemental sulfur and / or lithium polysulfide to lithium sulfide at the cathode, wherein at least a portion of the lithium polysulfide is partially captured by the defective metal-organic framework; (3) the charge cycle comprises oxidation of lithium sulfide at the cathode to lithium polysulfide and / or elemental sulfur, wherein at least a portion of the lithium polysulfide in the oxidation reaction is the lithium polysulfide captured during the discharge cycle; or (ii) providing a lithium-sulfur battery having a charge cycle and a discharge cycle, wherein (1) The lithium-sulfur battery comprises: (a) an anode comprising lithium, (b) electrolyte, and (c) a cathode comprising sulfur and a plurality of defective metal organic framework portions comprising at least one defect selected from a metal coordination site and a chemical anchor substituent capable of functionalizing a polysulfide thereto; (2) the discharge cycle comprises reducing elemental sulfur and / or lithium polysulfide to lithium sulfide at the cathode, wherein at least a portion of the polysulfide is captured into metal organic framework chemical anchor sites by functionalization; and (3) the charge cycle comprises oxidation of lithium sulfide at the cathode to lithium polysulfide and / or elemental sulfur, wherein at least a portion of the lithium polysulfide in the oxidation reaction is the lithium polysulfide captured during the discharge cycle; or (iii) providing a lithium-sulfur battery having a charge cycle and a discharge cycle, wherein (1) The lithium-sulfur battery comprises: (a) an anode comprising lithium, (b) electrolyte, and (c) a cathode comprising sulfur and (I) a plurality of defective metal organic framework portions comprising at least one defect independently selected from a metal coordination site and a proton site, wherein each defect independently allows for the capture of lithium ions, and (II) a plurality of defective metal-organic framework portions comprising at least one defect selected from a metal coordination site and a chemical anchor substituent capable of functionalizing a polysulfide thereto; (2) the discharge cycle comprises reducing elemental sulfur and / or lithium polysulfide to lithium sulfide at the cathode, wherein at least a portion of the lithium polysulfide is captured into metal organic framework chemical anchor sites by functionalization; and (3) the charge cycle comprises oxidation of lithium sulfide at the cathode to lithium polysulfide and / or elemental sulfur, wherein at least a portion of the lithium polysulfide in the oxidation reaction is the lithium polysulfide captured during the discharge cycle, The metal of the metal organic framework part is selected from zirconium, hafnium, cesium, copper, zinc, titanium, iron, vanadium, molybdenum, niobium and chromium.
33. The method of claim 32, wherein: The defective metal organic framework portion differs from the parent metal organic framework portion in the presence of the defects.
34. The method of claim 32, wherein the metal is zirconium.
35. The method of claim 32, wherein a portion of the plurality of defective metal organic framework portions defined in step (i)(1)(c) and step (iii)(1)(c)(I) comprises at least one defect, wherein the at least one defect is a proton site.
36. The method of claim 35, wherein each proton site is independently selected from a hydroxyl group and a H2O group.
37. The method of claim 32, wherein the defect is a chemical anchor substituent functionalized to a protonic site and selected from the group consisting of thiophosphate, thiogermanate, and thioarsenate.
38. The method of claim 37, wherein the chemical anchor substituent is a thiophosphate.
39. The method of any one of claims 32 to 38, wherein the lithium-sulfur battery has a capacity retention of at least 60% after 20 charge-discharge cycles.
40. The method of any one of claims 32 to 38, wherein the lithium-sulfur battery has a capacity of at least 800 mAh g after 20 charge-discharge cycles. -1 absolute capacity.
41. An ambient temperature sodium-sulfur battery comprising: (i) an anode comprising sodium; (ii) electrolyte; as well as (iii) a cathode comprising sulfur and a plurality of defective metal organic framework portions, wherein: (1) wherein each defective metal organic framework portion independently comprises at least one defect independently selected from a metal coordination site and a proton site; and (2) wherein each defect independently allows for the capture of battery anode metal ions or is functionalized as a chemical anchor substituent for the capture of polysulfides, The metal of the metal organic framework part is selected from zirconium, hafnium, cesium, copper, zinc, titanium, iron, vanadium, molybdenum, niobium and chromium.
42. The sodium-sulfur battery of claim 41, wherein the defective metal organic framework portion differs from a parent metal organic framework portion in the presence of the defects.
43. The sodium-sulfur battery of claim 41, wherein the metal of the metal organic framework portion is zirconium.
44. The sodium-sulfur battery of any one of claims 41 to 43, wherein a portion of the plurality of defective metal organic framework portions comprises at least one defect, the at least one defect being a proton site.
45. The sodium-sulfur battery of claim 44, wherein each proton site is independently selected from a hydroxyl group and a H2O group.
46. The sodium-sulfur battery of claim 44, wherein a portion of the proton sites are functionalized with sodium.
47. The sodium-sulfur battery of any one of claims 41 to 43, wherein a portion of the plurality of defective metal organic framework portions comprises defects that are metal coordination sites, defects that are chemical anchor substituents functionalized to the proton sites for capturing polysulfides, or a combination thereof.
48. The sodium-sulfur battery of claim 47, wherein the chemical anchor substituent is selected from thiophosphate, thiogermanate, and thioarsenate.
49. The sodium-sulfur battery of claim 48, wherein the chemical anchor substituent is thiophosphate.
50. A sodium-sulphur battery according to any one of claims 41 to 43, wherein the cathode comprises a combination of a metal organic framework comprising defects as defined in any one of claims 45 to 46 and a metal organic framework comprising defects as defined in any one of claims 48 to 49.
51. A solid material having sodium conductivity, the solid material comprising sodium and a plurality of defective metal organic framework portions: (i) wherein each defective metal organic framework portion independently comprises a defect selected from a metal coordination site and a proton site; and (ii) wherein said sodium is bound to or trapped by said defect, The metal of the metal organic framework part is selected from zirconium, hafnium, cesium, copper, zinc, titanium, iron, vanadium, molybdenum, niobium and chromium.
52. The solid material of claim 51, wherein the defective metal organic framework portion differs from a parent metal organic framework portion in the presence of the defects.
53. The solid material of claim 51, wherein the metal is zirconium.
54. The solid material of any one of claims 51 to 53, wherein a portion of the plurality of defective metal organic framework portions comprises at least one defect, the at least one defect being a proton site.
55. The solid material of claim 54, wherein each proton site is independently selected from a hydroxyl group and a H2O group.
56. A solid material according to any one of claims 51 to 53, 55, wherein the solid material is an electrolyte.
57. A method of using an ambient temperature sodium-sulfur battery, the method comprising: (i) providing an ambient temperature sodium-sulfur battery, the sodium-sulfur battery having a charge cycle and a discharge cycle, wherein (1) The sodium-sulfur battery comprises: (a) an anode comprising sodium, (b) electrolyte, and (c) a cathode comprising sulfur and a plurality of defective metal organic framework portions comprising at least one defect independently selected from a metal coordination site and a proton site, wherein each defect independently allows for the capture of sodium ions; (2) the discharge cycle comprises reducing elemental sulfur and / or sodium polysulfide to sodium sulfide at the cathode, wherein at least a portion of the sodium polysulfide is partially captured by the defective metal-organic framework; (3) the charging cycle comprises oxidation of sodium sulfide to sodium polysulfide and / or elemental sulfur at the cathode, wherein at least a portion of the sodium polysulfide in the oxidation reaction is the sodium polysulfide captured in the discharging cycle; or (ii) providing an ambient temperature sodium-sulfur battery, the sodium-sulfur battery having a charge cycle and a discharge cycle, wherein (1) The sodium-sulfur battery comprises: (a) an anode comprising sodium, (b) electrolyte, and (c) a cathode comprising sulfur and a plurality of defective metal organic framework portions comprising at least one defect selected from a metal coordination site and a chemical anchor substituent capable of functionalizing a polysulfide thereto; (2) the discharge cycle comprises reducing elemental sulfur and / or sodium polysulfide to sodium sulfide at the cathode, wherein at least a portion of the polysulfide is captured by functionalization into metal organic framework chemical anchor sites; and (3) the charging cycle comprises oxidation of sodium sulfide to sodium polysulfide and / or elemental sulfur at the cathode, wherein at least a portion of the sodium polysulfide in the oxidation reaction is the sodium polysulfide captured in the discharging cycle; or (iii) providing an ambient temperature sodium-sulfur battery having a charge cycle and a discharge cycle, wherein (1) The sodium-sulfur battery comprises: (a) an anode comprising sodium, (b) electrolyte, and (c) a cathode comprising sulfur and (I) a plurality of defective metal organic framework portions comprising at least one defect independently selected from a metal coordination site and a proton site, wherein each defect independently allows for the capture of sodium ions, and (II) a plurality of defective metal-organic framework portions comprising at least one defect selected from a metal coordination site and a chemical anchor substituent capable of functionalizing a polysulfide thereto; (2) the discharge cycle comprises reducing elemental sulfur and / or sodium polysulfide to sodium sulfide at the cathode, wherein at least a portion of the sodium polysulfide is captured into metal organic framework chemical anchor sites by functionalization; and (3) the charging cycle comprises oxidizing sodium sulfide at the cathode to sodium polysulfide and / or elemental sulfur, wherein at least a portion of the sodium polysulfide in the oxidation reaction is the sodium polysulfide captured in the discharging cycle, The metal of the metal organic framework part is selected from zirconium, hafnium, cesium, copper, zinc, titanium, iron, vanadium, molybdenum, niobium and chromium.
58. The method of claim 57, wherein the defective metal organic framework portion differs from a parent metal organic framework portion in the presence of the defects.
59. The method of claim 57, wherein the metal is zirconium.
60. The method of claim 57, wherein a portion of the plurality of defective metal organic framework portions defined in step (i)(1)(c) and step (iii)(1)(c)(I) comprises at least one defect, wherein the at least one defect is a proton site.
61. The method of claim 60, wherein each proton site is independently selected from a hydroxyl group and a H2O group.
62. The method of claim 57, wherein the defect is a chemical anchor substituent functionalized to a protonic site and selected from the group consisting of thiophosphate, thiogermanate, and thioarsenate.
63. The method of claim 62, wherein the chemical anchor substituent is a thiophosphate.
Citation Information
Patent Citations
Solid electrolyte for lithium ion battery and application thereof
CN102738510A
Preparation method for lithium-sulfur battery positive electrode material adopting metal-organic framework material as sulfur carrier
CN103236542A